Polypropylene-based resin composition and manufacturing method thereof, and manufacturing method of polypropylene resin film

A specific blend of branch-shaped and standard polypropylene resins with defined molecular properties addresses the challenges of strength and optical properties in polypropylene films, resulting in high-intensity films with excellent cut properties and cost-effective production.

JP2025016850APending Publication Date: 2025-02-05JAPAN POLYPROPYLENE CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023119598
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-07-24
Publication Date
2025-02-05

AI Technical Summary

Technical Problem

Existing polypropylene resin films face challenges in achieving high strength, excellent optical characteristics, and good cut properties while maintaining lightweight and cost-effective production, with conventional additives leading to defects or reduced film integrity.

Method used

A polypropylene resin composition combining a specific branch-shaped polypropylene resin (X) with a specific polypropylene resin (Y) in a specific ratio, characterized by defined molecular weight distribution, melt flow rate, and branch characteristics, which enhances strength and optical properties.

Benefits of technology

The composition enables the production of non-oriented films with high intensity, excellent optical characteristics, and superior cut properties, while maintaining lightweight and cost-effectiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025016850000006
    Figure 2025016850000006
  • Figure 2025016850000007
    Figure 2025016850000007
  • Figure 2025016850000008
    Figure 2025016850000008
Patent Text Reader

Abstract

To provide a polypropylene-based resin composition capable of forming non-drawn films with high strength, excellent optical properties, and excellent straight cuttability.SOLUTION: There is provided a polypropylene-based resin composition comprising a branched polypropylene-based resin (X) having the following characteristics (X-1) to (X-4) and a polypropylene-based resin (Y) having the following characteristic (Y-1) (excluding the branched polypropylene-based resin (X)) with an amount of the resin (X) being 1 mass% to 95 mass% based on a total mass of 100 mass% of the resin (X) and the resin (Y). Characteristic (X-1): MFR is 0.1 g / 10 min to 100 g / 10 min. Characteristic (X-2): Mz / Mw is 2.5 to 4.0. Characteristic (X-3): branching index g' (1,000,000) is 0.60 to 0.75. Characteristic (X-4): the flow activation energy (Ea) kJ / mol and MFR satisfy the following Formula (1); [Formula (1): Ea≥-12.5×log(MFR)+66]. Characteristic (Y-1): MFR is 0.1 g / 10 min or more and less than 10 g / 10 min.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polypropylene resin composition and a method for producing the same, and a method for producing a polypropylene resin film. [Background technology]

[0002] In recent years, there has been a demand for thinner films from the viewpoints of reducing raw material costs, improving productivity through high-speed film production, cost reduction through weight reduction, and environmental issues. However, excessive thinning leads to a decrease in the stiffness, or strength, of the film. A decrease in strength not only adversely affects transportability and unwinding from a roll during film processing, but also reduces the inherent functions of the final package, such as protecting the contents and maintaining the shape.

[0003] In order to solve the problem of strength loss caused by thinning, the strength of the film can be increased. Major methods for increasing strength include adding a nucleating agent, which is a crystallization promoter (e.g., Patent Documents 1, 2, and 6), adding an ethylene polymer having a specific density and a specific MFR (e.g., Patent Document 3), and adding a resin reinforcing filler such as talc, carbon nanofiber, or cellulose nanofiber. However, when inorganic nucleating agents are added, they act as foreign matter and cause a defect in the appearance of the film known as fish eyes, while when organic network nucleating agents are added, there is a risk that the contents of the package will be contaminated by low molecular weight components derived from the nucleating agent. Furthermore, when an ethylene polymer is added, there is a concern that the strength of the film may decrease and the occurrence of fish eyes may worsen due to gelation of polyethylene. Furthermore, when resin-reinforcing fillers are added, not only do they significantly change the feel, texture, and optical properties, but they also increase the specific gravity, making them unsuitable for the purpose of reducing weight.

[0004] It is also possible to increase the strength of the film by adjusting the film-forming conditions, such as by promoting oriented crystallization by lowering the extrusion temperature or promoting crystal growth by increasing the cooling and solidification temperature (e.g., Patent Document 4). However, this is not a preferred method because it results in a deterioration in the thickness accuracy of the obtained film and changes in the optical properties.

[0005] Also, in order to provide a polypropylene resin composition for high-rigidity films having an excellent balance between rigidity and transparency, a method of adding an alicyclic hydrocarbon resin component such as a petroleum resin to a polypropylene resin has been proposed (Patent Document 5). However, the alicyclic hydrocarbon resin component is expensive and is not suitable for the purpose of increasing rigidity for cost reduction, such as improving productivity or reducing weight.

[0006] On the other hand, in order to impart straight cuttability to a non-oriented film, there is mentioned a laminated film in which a surface layer (A) containing a polypropylene resin as the main resin component and containing a cyclic olefin resin, an intermediate layer (B) containing a linear low density polyethylene and a cyclic olefin resin, and a heat seal layer (C) containing a linear low density polyethylene as the main resin component are laminated (Patent Document 7).

[0007] Therefore, in view of the above-mentioned conventional techniques, it is preferable to increase the strength of a film by using the composition of the polymer itself; however, a film made of a polypropylene composition that has both high strength and excellent straight cut properties while retaining the functions that the film should have, such as optical properties, has not yet been found. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 8-3364 [Patent Document 2] Japanese Patent Application Publication No. 9-118776 [Patent Document 3] JP 2008-127487 A [Patent Document 4] JP 2011-236357 A [Patent Document 5] JP 2016-11380 A [Patent Document 6] Patent Publication No. 2021-4359 [Patent Document 7] Patent Publication No. 2021-102300 Summary of the Invention [Problem to be solved by the invention]

[0009] In view of the above-mentioned problems, an object of the present invention is to provide a polypropylene resin composition capable of being molded into a non-oriented film having high strength and excellent optical properties and also excellent straight cutability, a method for producing the same, and the film. [Means for solving the problem]

[0010] As a result of intensive research, the present inventors have found that a non-oriented film using a polypropylene resin composition containing a specific polypropylene resin (Y) in combination with a branched polypropylene resin (X) having specific properties has high strength, excellent optical properties such as transparency and gloss, and excellent straight cutting properties, and have thus completed the present invention. The present invention relates to the following: <1> ~ <4> Regarding. <1> A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following characteristic (Y-1) (excluding the branched polypropylene resin (X)), A polypropylene resin composition comprising the resin (X) in an amount of 1% by mass to 95% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. <2> The polypropylene resin (Y) is a homopolymer of propylene. <1> The polypropylene resin composition according to claim 1. <3> A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A method for producing a polypropylene-based resin composition, comprising the step of dry-blending a polypropylene-based resin (Y) having the following property (Y-1): Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. <4> The above <1> or <2> 2. A method for producing a film, comprising the step of molding the polypropylene-based resin composition according to claim 1 by a cast molding method. Effect of the Invention

[0011] According to the present invention, there are provided a polypropylene resin composition capable of being molded into a non-oriented film having high strength and excellent optical properties and also excellent straight cutability, a method for producing the same, and a film. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a diagram illustrating the baseline and intervals of a chromatogram in GPC. [Diagram 2] FIG. 2 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for the branched polypropylene resins (X1) to (X3) used in each example and the comparative branched polypropylene resins (CX1) to (CX3) are plotted. [Diagram 3] FIG. 3 is a diagram showing an example of an integrated molecular weight distribution curve. [Figure 4] 1 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for branched polypropylene resins (X1) to (X3) used in each example and comparative branched polypropylene resins (CX1) to (CX3) are plotted. [Diagram 5] FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum take-up speed (MaxDraw) at 230° C., and data for the branched polypropylene resins (X1) to (X3) used in each example and the comparative branched polypropylene resins (CX1) to (CX3) are plotted. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] I. Polypropylene resin composition The polypropylene resin composition of the present invention comprises a branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following characteristic (Y-1) (excluding the branched polypropylene resin (X)), The resin (X) is contained in an amount of 1% by mass to 95% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g'(million) is 0.60~0.75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity satisfy the following formula (1). Ea≧-12.5×log(MFR)+66 Equation (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min.

[0014] The polypropylene resin composition of the present invention contains a specific polypropylene resin (Y) in combination with a branched polypropylene resin (X) having the above-mentioned properties (X-1) to (X-4), i.e., a specific branched polypropylene resin (X) having specific molecular weight distribution and branching distribution and high Ea corresponding to MFR, and thereby can be molded into a non-oriented film having high strength, excellent optical properties, and excellent straight cutability.

[0015] The polypropylene resin (Y) is suitable for producing a non-stretched film because its MFR measured at 230° C. under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min. However, when a non-stretched film is produced using the polypropylene resin (Y) alone, the optical properties and straight cutability of the film become insufficient, as shown in the comparative example described later. In contrast, in the present invention, the polypropylene resin (Y) having the specific MFR is combined with the branched polypropylene resin (X) having the specific properties. The branched polypropylene resin (X) having the specific characteristics contains a multi-branched molecule having a molecular structure in which a large number of branch chains are introduced in the medium to high molecular weight region. On the other hand, it is a branched polypropylene resin that reduces ultra-high molecular weight components with extremely long relaxation times, and further has a favorable relationship between the flow activation energy (Ea) and MFR obtained by measuring dynamic viscoelasticity, which is an index of branching characteristics. The branched polypropylene resin (X) specified as above shows a relaxation time distribution in which many components have a relatively short relaxation time and few components have an extremely long relaxation time, so that local orientation crystallization originating from the entanglement point of molecular chains is unlikely to occur, and it is possible to suppress the non-uniformity of orientation crystallization. Therefore, the extensibility that allows the resin to be stretched widely, thinly and uniformly in a molten state is improved, and even if the film is thinned, the decrease in strength is suppressed, and the strength is high and the optical properties are excellent. Furthermore, it is considered that the rigidity of the film is improved and the stress applied at the time of cutting is less likely to concentrate and disperse at the cut, so that an unstretched film with excellent linear cutability can be obtained.

[0016] The present invention will be described in detail below. In this specification, the use of "to" indicating a range of values ​​means that the values ​​before and after the range include the lower limit and upper limit. In this specification, the upper and lower limit values ​​of the numerical ranges may be arbitrarily combined, and the preferred ranges of the respective properties may be arbitrarily combined. In the present invention, logarithms are expressed in the common logarithm sense, ie, to the base 10. In the present invention, unless otherwise specified, the contents of the branched polypropylene resin (X) and the polypropylene resin (Y) in the resin composition are represented by mass ratios when the total mass of the branched polypropylene resin (X) and the polypropylene resin (Y) is taken as 100 mass%.

[0017] The polypropylene resin composition of the present invention contains the branched polypropylene resin (X) and a polypropylene resin (Y) having the characteristic (Y-1) (excluding the branched polypropylene resin (X)), in an amount of 1% by mass to 95% by mass of the resin (X) relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may further contain other components such as additives described later.

[0018] 1. Branched polypropylene resin (X) The branched polypropylene-based resin (X) used in the present invention may be a homopolymer of propylene, or a copolymer of propylene and one or more comonomers selected from α-olefin comonomers having 2 to 20 carbon atoms other than propylene, such as ethylene, 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene, etc. The branched polypropylene resin (X) used in the present invention may be a branched propylene polymer comprising propylene, ethylene, and 0 to 11 mol % of an α-olefin having 4 or more carbon atoms.

[0019] 1-1. Characteristics of branched polypropylene resin (X) Characteristics (X-1): The branched polypropylene resin (X) used in the present invention has a melt flow rate (MFR) of 0.1 g / 10 min to 100 g / 10 min measured at a temperature of 230° C. under a load of 2.16 kg, from the viewpoint of ease of molding the branched polypropylene resin composition by a cast method. The MFR is preferably 1.0 g / 10 min or more, and may be 3.0 g / 10 min or more, while the MFR is preferably 80 g / 10 min or less, more preferably 50 g / 10 min or less, further preferably 40 g / 10 min or less, and may be 30 g / 10 min or less. In the present invention, the MFR is a value measured by pelletizing the branched polypropylene resin (X) and measuring the MFR at 230°C and a load of 2.16 kgf in accordance with JIS K7210-1:2014 "Plastics - Determination of melt mass-flow rate (MFR) and melt volume-flow rate (MVR) of thermoplastics - Part 1: Standard test method". The pelletization is performed in the same manner as the "granulation" described in the examples below. The MFR of the branched polypropylene resin can be adjusted by (i) changing the temperature and / or pressure during polymerization of the polypropylene resin and / or (ii) adding hydrogen or other chain transfer agents to the monomers during polymerization of the polypropylene resin.

[0020] Characteristics (X-2): From the viewpoint of ease of molding the branched polypropylene resin composition by a cast method, the branched polypropylene resin (X) used in the present invention has a ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) of 2.5 to 4.0. Mz, Mw, and number average molecular weight (Mn) are each indices that represent the average molecular weight of a polymer. Mz is an index of the average molecular weight with a high specific gravity on the high molecular weight side, Mn is an index of the average molecular weight with a high specific gravity on the low molecular weight side, and Mw is an index of the average molecular weight in between. In addition, the respective ratios, Mw / Mn and Mz / Mw, are indices of the spread of the molecular weight distribution of the polymer.

[0021] In the branched polypropylene resin (X), from the viewpoints of the presence of an appropriate amount of a component having a long relaxation time and suppressing a decrease in melt tension, Mz / Mw is 2.5 to 4.0. The upper limit of Mz / Mw is preferably 3.6 or less, more preferably 3.4 or less, and even more preferably 3.2 or less. The lower limit of Mz / Mw is preferably 2.6 or more, more preferably 2.8 or more, and even more preferably 2.9 or more.

[0022] In addition, the branched polypropylene resin (X) used in the present invention may have a ratio of Mw to Mn (Mw / Mn) obtained by GPC of 3.0 to 7.0 from the viewpoint of ease of molding the branched polypropylene resin composition by a casting method. The upper limit of Mw / Mn may be 6.0 or less, 5.0 or less, 4.5 or less, or 4.3 or less. On the other hand, the lower limit of Mw / Mn may be 3.2 or more, or 3.3 or more. Furthermore, from the viewpoint of ease of molding the branched polypropylene resin composition by a cast method, the Mw of the branched polypropylene resin (X) used in the present invention may be 150,000 to 350,000, 180,000 to 330,000, or 200,000 to 320,000.

[0023] The values ​​of Mz, Mw, Mn, Mw / Mn, and Mz / Mw are all obtained by GPC. The details of the measurement method and measuring equipment are as follows. Apparatus: Waters GPC (ALC / GPC, 150C) Detector: FOXBORO MIRAN, 1A, IR detector (measurement wavelength: 3.42 μm) Column: Showa Denko AT-806MS (3 columns) Mobile phase solvent: o-dichlorobenzene (ODCB) ·Measurement temperature: 140℃ ·Flow rate: 1.0mL / min ·Injection volume: 0.2mL The measurement sample is prepared as follows: A 1 mg / mL solution is prepared using the sample and ODCB (containing 0.5 mg / mL dibutylhydroxytoluene (BHT)), and the sample is dissolved at 140° C. for about 1 hour to prepare the measurement sample. The baseline and intervals of the obtained chromatogram are defined as shown in Figure 1. The retention volume obtained by GPC measurement is converted to molecular weight using a calibration curve prepared in advance using standard polystyrenes, all of which are the following brands manufactured by Tosoh Corporation: F380, F288, F128, F80, F40, F20, F10, F4, F1, A5000, A2500, and A1000. Each standard was dissolved in ODCB (containing 0.5 mg / mL BHT) to a concentration of 0.5 mg / mL, and 0.2 mL of the solution was injected to create a calibration curve. The calibration curve was calculated using a cubic equation obtained by approximating the curve using the least squares method. Viscosity formula used for conversion to molecular weight: [η] = K × M α The following numerical values ​​are used: PS:K=1.38×10 -4 , α=0.7 PP:K=1.03×10 -4 , α=0.78

[0024] The average molecular weight, molecular weight distribution (Mz, Mw, Mn, Mw / Mn, Mz / Mw) and balance thereof of the branched polypropylene resin (X) measured by GPC can be adjusted by polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc.

[0025] Characteristics (X-2-2): The branched polypropylene resin (X) used in the present invention preferably has an integral molecular weight distribution curve obtained by GPC, in which the ratio (W2 million / W1 million) of the proportion of components having a molecular weight of 2 million or more (W2 million) to the proportion of components having a molecular weight of 1 million or more (W1 million) satisfies the following formula (2): (W2 million / W1 million)<-0.05×log(MFR)+0.34 Formula (2) W2 million / W1 million is the ratio of the amount of components in the high molecular weight region to the amount of components with even higher molecular weights. The above formula (2) is considered to be a function in which W2 million / W1 million is negatively correlated with an increase in MFR, and based on data from examples and comparative examples having the same level of MFR as the examples, an approximate relationship between W2 million / W1 million and MFR that distinguishes between examples that can solve the problem and comparative examples of the prior art that cannot solve the problem was determined (see Figure 2). Satisfying the formula (2) means that W2 million / W1 million is less than a specific value in terms of MFR. In other words, it means that the amount of components with a molecular weight of 2 million or more, which is higher than the amount of components with a molecular weight of 1 million or more, is relatively small. When W2 million / W1 million is in the above range in terms of MFR, it is considered that the amount of components having a long relaxation time is prevented from becoming too large, and the extensibility is maintained. Therefore, it is preferable that the branched polypropylene resin (X) used in the present invention satisfies the above formula (2).

[0026] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00% by mass or more and 9.50% by mass or less. It is believed that the melt tension of the branched polypropylene resin (X) used in the present invention increases due to the presence of components in the high molecular weight range. Therefore, in the present invention, attention is focused on components having a molecular weight of 1 million or more, and the branched polypropylene resin (X) used in the present invention may have a W1 million of 1.00 mass% or more, or may be 2.00 mass% or more. On the other hand, it is believed that the presence of an appropriate amount of components in the high molecular weight range maintains an appropriate amount of components with long relaxation times and maintains extensibility. Therefore, W1 million may be 9.50 mass% or less, 8.00 mass% or less, 6.00 mass% or less, or 5.00 mass% or less.

[0027] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass % or less. As in the above, it is believed that the presence of an appropriate amount of components in the very high molecular weight range maintains the components with extremely long relaxation times appropriately, and also maintains extensibility. Therefore, in the present invention, attention is focused on components with a molecular weight of 2 million or more, and the branched polypropylene resin (X) used in the present invention may have a W2 million of 2.00 mass% or less, 1.00 mass% or less, or 0.70 mass% or less. The branched polypropylene resin (X) used in the present invention may have a W2 million of 0.05 mass% or more.

[0028] Furthermore, the branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.25 or less, 0.20 or less, or 0.17 or less. As mentioned above, when W2 million / W1 million is within the above range, it is believed that the components with long relaxation times are prevented from becoming too numerous, and ductility is maintained. The branched polypropylene resin (X) used in the present invention may have a W2 million / W1 million ratio of 0.02 or more, 0.03 or more, or 0.05 or more.

[0029] In the present invention, W1 million and W2 million are defined as the value obtained by subtracting from 1 the integral value up to a molecular weight (M) of 1 million (Log(M)=6.0) and up to a molecular weight (M) of 2 million (Log(M)=6.3) in an integrated molecular weight distribution curve (total amount normalized to 1) obtained by GPC, and multiplying the result by 100. An example of an integrated molecular weight distribution curve is shown in FIG. In the present invention, W1 million and W2 million of the branched polypropylene resin (X) can be adjusted by polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc., as described in the characteristic (X-2).

[0030] Characteristics (X-3): The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M absThe branching index g'(million) is 0.60~0.75. The branching index g' is the intrinsic viscosity [η] of a polymer with a long chain branching structure. br Intrinsic viscosity [η] of a linear polymer with the same molecular weight lin Ratio to ([η] br / [η] lin ) When a polymer molecule has long chain branches, it has a smaller radius of gyration and a smaller intrinsic viscosity than a linear polymer molecule of the same molecular weight, so g' is smaller than 1.0. Also, even if the amount of branching is the same, if the branch length is long, it has a smaller radius of gyration and a smaller intrinsic viscosity than a linear polymer molecule of the same molecular weight, so g' is smaller than 1.0. Linear polymers, by definition, have a g' of 1.0. The definition of g' is described in "Developments in Polymer Characterization-4" (JV Dawkins ed. Applied Science Publishers, 1984), and is a known indicator for those skilled in the art. g' was determined by using 3D-GPC. abs can be obtained as a function of In this specification, 3D-GPC refers to a GPC apparatus to which three detectors are connected. The three detectors are a differential refractometer (RI), a viscosity detector (Viscometer) and a multi-angle laser light scattering detector (MALLS).

[0031] The branched polypropylene resin (X) used in the present invention has an absolute molecular weight M abs Weight average molecular weight (Mw abs ) may be less than 1 million, and Mw abs From M abs It is considered that a branched structure in the high molecular weight region of 1,000,000 is preferable in terms of having a high melt tension. Therefore, the branched polypropylene resin (X) used in the present invention has a g' (1 million) of 0.75 or less, preferably 0.74 or less, and more preferably 0.72 or less.abs If the branched structure is present in an appropriate amount in the high molecular weight region of g'(1 million) and the branched chain length of the introduced branched structure is appropriate, it is considered that the amount of components with extremely long relaxation times is prevented from increasing too much, and extensibility can be maintained. Therefore, g'(1 million) is 0.60 or more, preferably 0.62 or more, and more preferably 0.65 or more. In this way, the branched polypropylene resin (X) used in the present invention has M abs It is believed that the amount of components with branched structures in the molecular weight region of 100,000,000 is appropriately large within a specific range, which increases the melt strength and increases the strain hardening index (SHI) and melt tension (MT) in the measurement of extensional viscosity as nonlinear viscoelastic properties. Even if the number of branches is large as a whole polymer, the amount of M corresponding to the high molecular weight component is abs If the amount of components having branches in the M = 1 million portion is small, the SHI does not become large. abs = 1 million, and furthermore, the branched chain length of the introduced branched structure is not too long, which is thought to suppress deterioration of ductility.

[0032] Characteristics (X-3-2): The branched polypropylene resin (X) used in the present invention is considered to be able to maintain extensibility by the presence of a suitable amount of components having a long relaxation time, similar to the above characteristic (X-3). Therefore, in the molecular weight distribution curve obtained by 3D-GPC, Mw abs Branching index g'(Mw abs ) may be 0.70 to 0.90. g'(Mw abs The lower limit of may be 0.73 or more, or 0.75 or more, and the upper limit may be 0.87 or less, or 0.86 or less.

[0033] Characteristics (X-3-3): The branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs) and g' (1 million) may satisfy the following formula (3): 0.10≦g'(Mw abs )-g'(1 million) Formula (3) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs It is believed that the large difference between g(1) and g'(1 million) results in a larger number of components with longer relaxation times, which in turn increases the melt strength. Furthermore, the branched polypropylene resin (X) used in the present invention has a molecular weight distribution curve obtained by 3D-GPC, in which g'(Mw abs ) and g' (1 million) may satisfy the following formula (3-2). g'(Mw abs )-g'(1 million)≦0.20 Formula (3-2) As described above, in the branched polypropylene resin (X) used in the present invention, g'(Mw abs It is considered preferable that the difference between g(1) and g'(1 million) is not too large, since this prevents the proportion of components with extremely long relaxation times from becoming too high, thereby improving extensibility. In addition, the branched polypropylene polymer of the present invention is considered to be preferable since the branching distribution is within the above range, making it possible to maintain a balance between melt strength and extensibility as a whole.

[0034] M abs The method for measuring the molecular weight distribution and the branching index at each molecular weight is as follows: The detectors are connected in the order of MALLS, RI, and Viscometer. Equipment: Alliance GPCV2000 (GPC equipped with RI and Viscometer) manufactured by Waters, DAWN-E (MALLS) manufactured by Technology Column: Tosoh GMHHR-H(S)HT (2 columns) Mobile phase solvent: 1,2,4-trichlorobenzene (with antioxidant Irganox 1076 (BASF Japan) added at a concentration of 0.5 mg / mL) ·Measurement temperature: 140℃ ·Flow rate: 1mL / min Sample concentration: 1mg / mL ·Injection volume: 0.2175mL M obtained from MALLS abs The root mean square radius of gyration (Rg) and the intrinsic viscosity ([η]) obtained from the Viscometer are calculated using the data processing software ASTRA (version 4.73.04) attached to MALLS, with reference to the following literature. References: 1.Developments in Polymer Characterization, vol.4. Essex: Applied Science; 1984. Chapter1. 2.Polymer, 45, 6495-6505(2004) 3.Macromolecules, 33, 2424-2436(2000) 4.Macromolecules, 33, 6945-6952(2000) g' is the intrinsic viscosity ([η] br ) and the intrinsic viscosity ([η] obtained by separately measuring a linear polymer lin ) and the ratio ([η] br / [η] lin ) is calculated as follows. Here, a commercially available homopolypropylene (Novatec PP (registered trademark) manufactured by Japan Polypropylene Corporation, grade name: FY6) was used as the linear polymer, and [η] lin [η] of linear polymer lin The logarithm of [η] has a linear relationship with the logarithm of the molecular weight, as known from the Mark-Houwink-Sakurada equation. lin can be obtained by extrapolating to the low molecular weight side or the high molecular weight side as appropriate.

[0035] In the present invention, the g' (million) and g' (Mw abs ), g'(Mw absAs explained in the characteristic (X-2), )-g' (million) can be adjusted by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc. Among them, it is preferable to adjust by selecting the catalyst type, and although there is no particular limitation, it is appropriate to adjust by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.

[0036] Among them, g'(Mw abs It is preferable that the condition where (g)-g' (million) satisfies the formula (3) or the formula (3-2) is adjusted by selecting a catalyst from a plurality of catalyst species or a plurality of metallocene compounds. For example, when a catalyst consisting of a single catalyst type or a single metallocene compound (hereinafter, sometimes collectively referred to as a single catalyst) is used instead of a catalyst consisting of multiple catalyst types or multiple metallocene compounds, it is considered that formula (3) or formula (3-2) is not satisfied. This is because, with a single catalyst, the molecular weight distribution of the macromonomer produced is narrow, and macromonomers with significantly different molecular weights are not supplied, so the value of formula (3) is expected to be small, or the value of formula (3-2) to be large. To explain this using Reference Example 2 as an example (see Table 2), g'(Mw abs ) is large, so Mw abs Since there are no components with short branched chains, it is estimated that the molecular weight of the macromonomer produced by this catalyst is high. On the other hand, since g' (1 million) is small, it is assumed that the molecular weight of the macromonomer produced by this catalyst is high. abs It is estimated that there are branched components due to macromonomers with large molecular weights in the range of g'(Mw = 1 million). Thus, in a single catalyst that produces macromonomers with a narrow molecular weight distribution, for example, abs )-g' (million) becomes large and equation (3-2) is not satisfied.

[0037] Characteristics (X-4): From the viewpoint of improving the quality of a film produced by a cast molding method, the branched polypropylene resin (X) used in the present invention has a flow activation energy (Ea) kJ / mol and MFR obtained by measuring the dynamic viscoelasticity that satisfy the following formula (1): Ea≧-12.5×log(MFR)+66 Equation (1)

[0038] In general, the viscosity of an object decreases as its temperature increases, and the logarithm of viscosity, lnη, is proportional to the reciprocal of absolute temperature, 1 / T, and it has long been known empirically that it can be expressed by the following formula (Chemical Dictionary, 2nd Edition, "Andrade's Viscosity Formula").

[0039]

number

[0040] This energy term Ea corresponds to the activation energy when the reaction rate in an Arrhenius chemical reaction is considered to be a flow, and is called the flow activation energy. "High Ea" means "the energy required to make the polymer flow is large." In the case of branched polypropylene resin (X), it is considered that if the amount of branches is large or the branch length is long, the molecular chains become more entangled, and the energy required to make the molecular chains flow is large. In other words, Ea mainly depends on the amount and length of long chain branches in the polymer. In the branched polypropylene resin (X) used in the present invention, the relationship between Ea and MFR was specified, focusing on Ea as an index for obtaining appropriate branching characteristics in order to improve the quality and processability of a film produced by a cast molding method.

[0041] From the viewpoint of improving the quality and processability of the film, the branched polypropylene resin (X) used in the present invention may have an Ea of 55.0 kJ / mol or more, or 58.0 kJ / mol or more, or may have an Ea of 70.0 kJ / mol or less.

[0042] Satisfying the formula (1) means that the branched polypropylene resin (X) used in the present invention has an Ea obtained by measuring the dynamic viscoelasticity of at least a specific value in proportion to the MFR. The branched polypropylene resin (X) used in the present invention has an Ea value corresponding to the MFR different from that of conventional propylene polymers, that is, satisfies the formula (1). If Ea is too small in relation to MFR, the branching characteristics including the branch amount, branch length, and branching distribution become inappropriate, and the extensibility when melted becomes poor. Therefore, the branched polypropylene resin (X) used in the present invention satisfies the above formula (1). More preferably, it may satisfy the following formula (1-2). Ea≧-12.5×log(MFR)+72 Equation (1-2)

[0043] Generally, when the fluidity of a molten resin is increased, Ea decreases, so it is desirable to have a branched polypropylene resin that has both the necessary fluidity and Ea, which is an index of branching characteristics suitable for improving extensibility when melted. A branched polypropylene resin (X) that has excellent fluidity and satisfies formula (1) can be said to have a high balance between the fluidity and branching characteristics of a molten resin. In addition, the above formula considers Ea to be a function that is negatively correlated with an increase in MFR, and based on data for the branched polypropylene resin (X) used in the examples of the present invention and the comparative branched polypropylene resin (CX) that has the same level of fluidity as the examples, an approximate relationship between Ea and MFR that distinguishes between examples that can solve the problem and comparative examples of the prior art that cannot solve the problem was determined (see Figure 4).

[0044] The branched polypropylene resin (X) used in the present invention is presumed to have a high flow activation energy (Ea) corresponding to the MFR, since the branching characteristics including the branch amount, branch length, and branch distribution are suitable for improving the extensibility during melting. It is believed that if Ea is high relative to MFR, the extrusion load during molding can be reduced more compared to branched polypropylene resins with the same MFR. The branched polypropylene resin (X) used in the present invention satisfies the above formula (1), and therefore can increase the extensibility while reducing the extrusion load during molding.

[0045] The upper limit of Ea in relation to the MFR is not particularly limited, but may satisfy the following formula (1-3) or may satisfy the following formula (1-4). Ea≦-12.5×log(MFR)+82 Equation (1-3) Ea≦-12.5×log(MFR)+77 Equation (1-4)

[0046] Ea is a value calculated from the shift factor (aT) when creating a master curve based on the temperature-time superposition principle in the measurement of melt viscoelasticity by the Arrhenius equation. In the present invention, the master curve is a curve showing the angular frequency (unit: rad / sec) dependency of the melt complex viscosity (unit: Pa·sec) at 200°C. Ea can be determined by the following method. First, for three temperatures of 180°C, 200°C, and 220°C, the melt complex viscosity-angular frequency curve of the branched polypropylene resin (X) at each temperature (T, unit: °C) is obtained. Based on the temperature-time superposition principle, each melt complex viscosity-angular frequency curve is superimposed on the melt complex viscosity-angular frequency curve at 200°C to obtain each shift factor (aT). From each temperature (T) and aT at each temperature (T), a linear approximation equation (the following equation (4)) of [ln(aT)] and [1 / (T+273.16)] is calculated by the least squares method. Next, Ea is obtained from the slope m of the linear equation and the following equation (5). ln(aT)=m(1 / (T+273.16))+n Equation (4) Ea = |0.008314 × m| Equation (5) aT: Shift factor Ea: Flow activation energy (unit: kJ / mol) T: Temperature (unit: °C) The above calculations may be carried out using commercially available software, such as Trios manufactured by TA Instruments. Note that aT is the amount of movement in the x-axis direction when the log-log curve of melt complex viscosity vs. angular frequency at each temperature (T) is moved in the x-axis (angular frequency) and y-axis (melt complex viscosity) directions and superimposed on the melt complex viscosity vs. angular frequency curve at 200°C. The melt complex viscosity-angular frequency curve is measured using a viscoelasticity measuring device (for example, ARES-G2 manufactured by TA Instruments) under a nitrogen atmosphere under the following conditions. The propylene polymer is compression molded at 180°C for 5 minutes while being careful not to trap air bubbles, to obtain a disk-shaped measurement sample having a thickness of 2.0 mm and a diameter of 25 mm. Measurements of the sample are performed at three temperatures, 180°C, 200°C, and 220°C, using parallel disks having a diameter of 25 mm that are kept at each temperature, after which the measurement sample having a thickness of 2.0 mm is compressed to a thickness of 1.5 mm. Geometry: Parallel plate Plate diameter: 25mm Plate spacing: 2mm Strain: 5% Angular frequency: 0.01~100rad / sec

[0047] In the present invention, the Ea and MFR of the branched polypropylene resin (X) can satisfy the above formula (1) by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc., as explained in the characteristic (X-2). Among these, it is preferable to adjust by selecting the catalyst type, and although there is no particular restriction, it is appropriate to adjust by selecting the catalyst type in a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds.

[0048] Characteristics (X-5): The branched polypropylene resin (X) used in the present invention is 13 The meso triad fraction (mm) measured by C-NMR is preferably 95.0% or more and less than 99.0%. Characteristics (X-5-2): In addition, the branched polypropylene resin (X) used in the present invention preferably has a heterogeneous bond ([2,1 bond]) content of 0 mol % to 0.30 mol % and a heterogeneous bond ([1,3 bond]) content of 0 mol % to 0.25 mol %.

[0049] The crystallinity of the branched polypropylene resin (X) is affected by the stereoregularity indicated by the mesotriad fraction (mm) and mesopentad fraction (mmmm) and the regioregularity indicated by [2,1 bond] and [1,3 bond]. In other words, crystallization proceeds by folding back the lamellae from the irregularity-defective parts (sterically irregular bonds and heterogeneous bonds). When the branched polypropylene resin (X) used in the present invention has a stereoregularity and a regioregularity within the above ranges, it is believed that the fluidity of the resin during gradual cooling and solidification during molding and the melt tension during solidification are improved due to a crystallization process caused by shear or elongation deformation.

[0050] In order to improve the melt tension of the branched polypropylene resin (X) when solidified, the mm of the branched polypropylene resin (X) used in the present invention is preferably 95.0% or more, more preferably 96.0% or more, and even more preferably 97.0% or more. On the other hand, if mm is too high, the rigidity and Young's modulus become high, and the film may become too stiff. Therefore, mm of the branched polypropylene resin (X) used in the present invention is preferably less than 99.0%, more preferably 98.5% or less, and more preferably 98.2% or less.

[0051] Similarly, from the viewpoint of improving the melt tension during solidification, the amount of [2,1 bond] in the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.30 mol%, more preferably 0 mol% to 0.25 mol%, even more preferably 0 mol% to 0.20 mol%, even more preferably 0.030 mol% to 0.25 mol%, and particularly preferably 0.05 mol% to 0.20 mol%. The upper limit of the amount of [2,1 bond] may be 0.15 mol% or less. In addition, in combination with the amount of [2,1 bond], the amount of [1,3 bond] in the branched polypropylene resin (X) used in the present invention is preferably 0 mol% to 0.25 mol%, more preferably 0 mol% to 0.20 mol%, even more preferably 0 mol% to 0.15 mol%, even more preferably 0.05 mol% to 0.20 mol%, and particularly preferably 0.10 mol% to 0.15 mol%.

[0052] 13 The methods for measuring and calculating the amounts of mm, [2,1 bond] and [1,3 bond] measured by C-NMR are as follows. A 200 mg sample is placed in an NMR sample tube with an inner diameter of 10 mm together with 2.4 ml of o-dichlorobenzene / deuterated bromide benzene (C6D5Br) = 2 / 1 (volume ratio) and hexamethyldisiloxane, a chemical shift standard substance, and dissolved uniformly in a block heater at 150 °C to prepare a measurement sample. ( 1 H-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 4.5° Pulse Interval: 2 seconds Number of times of accumulation: 1024 times Chemical shift: The chemical shift is set to 0.09 ppm for the proton signal of hexamethyldisiloxane, and the chemical shifts of the signals due to other protons are based on this. ( 13 C-NMR) Equipment: Bruker Biospin AV400 NMR system Probe: 10mmφ cryo-probe Sample temperature: 120℃ Pulse angle: 45° Pulse Interval: 17.2 seconds Number of times: 3072 Decoupling conditions: Broadband decoupling method Chemical shift: Chemical shifts of hexamethyldisiloxane 13 The C signal was set to 1.98 ppm, and the other 13 The chemical shifts of the C signals are based on this.

[0053] The meso triad fraction (mm) of three propylene units is 13 Measured by C-NMR 13 The integrated intensity of the C signal can be calculated by substituting it into the following equation (6). mm(%)=I mm ×100 / (I mm +3×I mrrm ) Formula (6) Here I mm is assigned to the mm bonding mode of three propylene units. 13 The integrated intensity of the C signal is shown in Fig. 1. The integrated intensity of the signal with a chemical shift in the range of 23.6 to 21.1 ppm (hereinafter referred to as "I 23.6~21.1 " is used as the calculation. mrrm is assigned to the 5-propylene unit sequence as the mrrm bond mode. 13 C represents the integrated intensity of the signal, I 19.9~19.7 The value is shown below. Spectral assignment can be done with reference to Polymer Jounral, vol. 16, p. 717 (1984), Asakura Publishing, Macromolecules, vol. 8, p. 687 (1975), and Polymer, vol. 30, p. 1350 (1989). The chemical shift range shifts slightly depending on the molecular weight of the polymer, but it is easy to distinguish the regions.

[0054] The amount of [2,1 bond] and [1,3 bond] is 13 Measured by C-NMR 13It is calculated using the integrated intensity of the C signal according to the following formula. [2,1 bond] amount (mol%)=I 2,1-P ×100 / (I 1,2-P +I 2,1-P +I 1,3-P ) [1,3 bond] amount (mol%)=I 1,3-P ×100 / (I 1,2-P +I 2,1-P +I 1,3-P ) Here, I 1,2-P , I 2,1-P , I 1,3-P are assigned to the bonding modes of [1,2 bond], [2,1 bond], and [1,3 bond] in the propylene units, respectively. 13 It represents the integrated intensity of the C signal and is calculated as follows: I 1,2-P =I 48.80~44.50 I 2,1-P =(I 34.68~34.63 +I 35.47~35.40 +I 35.94~35.70 ) / 2 I 1,3-P =I 37.50~37.20 / 2

[0055] The above properties (X-5) and (X-5-2) can be satisfied by adjusting polymerization conditions such as the selection of catalyst type, polymerization temperature, monomer concentration, and amount of hydrogen.

[0056] Characteristics (X-6): The branched polypropylene resin (X) used in the present invention has the following properties: 13 The number of long chain branches (LCB number) measured by C-NMR is preferably 0.1 to 0.5 per 1000 monomers, and more preferably 0.2 to 0.5 per 1000 monomers.

[0057] The number of LCBs is 13The number per 1000 propylene monomers is calculated using the following formula using the integrated signal intensities of the branch point carbon (methine carbon) at 31.72 to 31.66 ppm and three methylene carbons bonded to the branch point carbons (methine carbon) at 44.09 to 44.03 ppm, 44.78 to 44.72 ppm, and 44.90 to 44.84 ppm when the intensity of the methylene carbons in the propylene main chain at 49.00 to 44.33 ppm is normalized to 1000 by C-NMR. Number of LCBs = [(I 44.09~43.03 +I 44.78~44.72 +I 44.90~44.84 +I 31.72~31.66 ) / 4] / I 49.00~44.33 When calculating the LCB number 13 The C-NMR measurement was performed under the same conditions as in the above (X-5), except that the measurement conditions were changed as follows: 13 This can be done in the same manner as C-NMR measurement. Pulse Interval: 4.2 seconds -Number of times: 20,000

[0058] In order to satisfy the characteristic (X-6), the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, amount of hydrogen, etc. can be adjusted in the same manner as described for the characteristic (X-4).

[0059] Characteristics (X-7): The branched polypropylene resin (X) used in the present invention has a strain hardening index (SHI@1s -1 ) is preferably 0.70 to 2.50. Here, SHI@1s -1 is the extensional viscosity (η E In the measurement of the Hencky strain (ε) between 1 and 3, the horizontal axis is the logarithm of the Hencky strain (log(ε)) and the vertical axis is the logarithm of the extensional viscosity (log(η E ) is the slope when plotting In order to increase the melt tension to improve moldability and to improve extensibility, the SHI@1s of the branched polypropylene resin (X) used in the present invention is -1is preferably from 0.70 to 2.50, more preferably from 0.80 to 2.00, and further preferably from 1.00 to 1.80. Branched polypropylene resin (X) is SHI@1s -1 When SHI@1s is relatively large, the extensional viscosity increases due to the presence of components in the polymer that do not relax at high strain rates. Therefore, linear polymers that do not have strain hardening at high strain rates and SHI@1s -1 Compared to polymers with a smaller elongational viscosity, the melt tension is increased due to the higher elongational viscosity, which is thought to improve moldability in sheet molding, blow molding, thermoforming, and foam molding. From this viewpoint, the branched polypropylene resin (X) used in the present invention is SHI@1s -1 It is preferable that the ratio is 0.70 or more. Branched polypropylene resin (X) is SHI@1s -1 When SHI@1s is appropriately large, the amount of components that do not relax or components that relax for a long time is appropriately maintained, and the local progression of oriented crystallization starting from the entanglement points of molecular chains is suppressed, and extensibility is maintained. From this viewpoint, the branched polypropylene resin (X) used in the present invention has a SHI@1s -1 It is preferable that the ratio is 2.50 or less.

[0060] The strain hardening index (SHI) can be determined by measuring the uniaxial extensional viscosity as described in Polymer, Vol. 42, p. 8663 (2001). In the present invention, SHI@1s -1 is measured by the following method. Equipment: TA Instruments ARES-G2 Fixture: TA Instruments Extensional Viscosity Fixture ·Measurement temperature: 180℃ ·Strain rate: 1.0 / sec - Preparation of test specimen: A sheet of 18 mm x 10 mm and 0.7 mm thick was prepared by press molding.

[0061] To calculate the SHI, the above measurement method is used to obtain data on the time change in elongational viscosity at a predetermined constant strain rate, and the measurement data is plotted as log(ε) on the horizontal axis and log(η) on the vertical axis. E ) is plotted on a graph. Then, the slope of the extensional viscosity in the Hencky strain range between 1 and 3 is identified from the graph, and this slope is taken as the SHI at the strain rate under the measurement conditions.

[0062] The characteristic (X-7) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-4).

[0063] Characteristics (X-8): The branched polypropylene resin (X) used in the present invention preferably has a multi-branching index (MBI) of 0.20 or more in order to provide excellent extensibility when melted, and preferably has a MBI of 1.00 or less in order to obtain stability in melt tension by suppressing the strain rate dependency of strain hardening. The lower limit of the MBI is more preferably 0.26 or more, and the upper limit is more preferably 0.80 or less, and further preferably 0.60 or less. Here, MBI is the slope of a plot of the SHI of a polymer at strain rates of 0.1 / sec to 10 / sec, with the logarithm of the strain rate (log(dε / dt)) on the horizontal axis and the SHI at strain rates of 0.1 / sec to 10 / sec on the vertical axis. The SHI of a polymer changes with strain rate. The MBI indicates the dependence of the SHI on the strain rate. A larger MBI value means that the SHI increases more with increasing strain rate. To obtain the MBI, SHI is measured at multiple strain rates in the range of 0.1 / sec to 10 / sec, and the SHI at each strain rate is plotted on a graph with log(dε / dt) on the horizontal axis and SHI on the vertical axis. The slope of the approximation line of the plot in the range of strain rates from 0.1 / sec to 10 / sec is defined as the MBI. -1 , SHI@1.0s -1 , SHI@10.0s -1The slope of the line that was approximated by the least squares method for the plot of the three points was determined as the MBI.

[0064] The characteristic (X-8) can be satisfied by adjusting the polymerization conditions, such as the selection of catalyst type, polymerization temperature, monomer concentration, and hydrogen amount, in the same manner as described for the characteristic (X-4).

[0065] Characteristics (X-9): The branched polypropylene resin (X) used in the present invention may have a melt tension at 230°C (MT230) of 0.3 g to 15 g, or 0.5 g to 15 g, in order to obtain a propylene polymer having excellent extensibility while maintaining a melt tension necessary for molding. In the present invention, MT230 is defined as the tension detected at a pulley when a resin is extruded in a string-like form and wound around a roller under the following conditions using a melt tension tester (for example, Capilograph 1B manufactured by Toyo Seiki Seisakusho). ·Resin temperature: 230℃ Capillary: diameter 2.0mm, length 40mm Cylinder diameter: 9.55mm Cylinder extrusion speed: 20mm / min · Winding speed: 4.0m / min If the resin breaks at a winding speed of 4.0 m / min, the melt tension is deemed "unable to evaluate."

[0066] Characteristics (X-10): The branched polypropylene resin (X) used in the present invention may have a maximum draw speed (MaxDraw) m / min at 230° C. and an MFR that satisfy the relationship represented by the following formula (7). (MaxDraw)>200×log(MFR)-38 Equation (7) Here, MaxDraw is the melt tension measurement, in which the resin is extruded into a string shape and wound around a roller, and the winding speed is increased from 4.0 m / min to an acceleration of 18.1 mm / sec. 2 This is the winding speed just before the string-shaped resin breaks when the winding speed is gradually increased. If the resin breaks at a winding speed of 4.0 m / min, it is deemed "evaluation not possible." The melt extensibility can be evaluated using MaxDraw as an index, and the larger MaxDraw is, the better the extensibility is. In the present invention, MaxDraw was measured under the following conditions. Equipment: INSTRON capillary rheometer CEAST SR50 Capillary: diameter 2.0mm, length 40mm Barrel diameter: 15mm Barrel length: 290mm Cylinder extrusion speed: 20mm / min ·Resin temperature: 230℃

[0067] Generally, increasing the fluidity leads to excellent extensibility, but the melt tension decreases. Increasing the fluidity to provide excellent extensibility leads to the problem that the melt tension becomes insufficient. Therefore, it is desirable for the propylene-based polymer to have both the melt tension required for molding and excellent extensibility. The relationship between MaxDraw and MFR defined by the above formula (7) can be used as an index of extensibility commensurate with fluidity. Satisfying the above formula (7) indicates that the branched polypropylene-based resin (X) used in the present invention has excellent extensibility commensurate with fluidity compared to conventional propylene-based polymers. That is, in order to distinguish the branched polypropylene resin (X) used in the present invention from the conventional ones, the melt extensibility (MaxDraw) is considered to be a function positively correlated with the increase in fluidity (MFR), the parameters of the function are set, and the MaxDraw of the branched polypropylene resin (X) used in the present invention is shown to be larger in proportion to the MFR than the MaxDraw of the conventional propylene polymer defined by the function. Specifically, based on the data of the examples and comparative examples, the values ​​of MaxDraw and MFR that distinguish the examples from the comparative examples of the prior art are assumed, and the parameters of the relational equation that holds between the MaxDraw and MFR are determined by the least squares method (see FIG. 5).

[0068] 1-2. Manufacturing method of branched polypropylene resin (X) The method for producing the branched polypropylene resin (X) used in the present invention is not particularly limited as long as it is a method that can produce a branched polypropylene resin (X) having the above-mentioned properties that are characteristic of the present invention. However, a macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is suitable. The present inventors speculate that the mechanism of the macromonomer copolymerization method using a catalyst containing a plurality of metallocene compounds is as follows. When polymerization is performed using a catalyst containing a metallocene compound (referred to as compound 1) that forms a catalyst that mainly produces a macromonomer and a metallocene compound (referred to as compound 2) that forms a catalyst that mainly copolymerizes a macromonomer and a propylene monomer to produce a polymer having a branched chain, the following polymerization behavior is observed. By using a propylene polymerization catalyst containing compound 1 and compound 2, it is possible to obtain a polymer having a molecular weight range that includes a molecular weight distribution that is a combination of the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 1 (catalyst 1) and the molecular weight and molecular weight distribution of a polymer produced from a catalyst containing compound 2 (catalyst 2). In the process of forming the branched structure, when the polymer produced from catalyst 1 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 1), and further, a copolymer of propylene and macromonomer 1 is produced from catalyst 1, and a copolymer of propylene and macromonomer 1 is produced from catalyst 2. When the polymer produced from catalyst 2 has a terminal vinyl group, such a polymer containing a terminal vinyl group becomes a macromonomer (referred to as macromonomer 2), and further, a copolymer of propylene and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene and macromonomer 2 is produced from catalyst 2. Furthermore, when the polymer produced from catalyst 1 is macromonomer 1 and the polymer produced from catalyst 2 is macromonomer 2, furthermore, a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 1, and a copolymer of propylene, macromonomer 1 and macromonomer 2 is produced from catalyst 2. In this way, depending on the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 1 of the polymer produced from catalyst 1, the molecular weight, molecular weight distribution, terminal vinyl ratio and copolymerizability of catalyst 2 of the polymer produced from catalyst 2, the quantitative ratio and steric positional relationship between catalyst 1 and catalyst 2, the average molecular weight, high molecular weight, and very high molecular weight of the branched polypropylene resin (X) as the final product, as well as the amount and branch distribution, change. That is, Mn, Mw, Mz, W 1 million, W 2 million, g' (1 million), g' (Mw abs ), [g'(Mw abs )-g'(million)], Ea, SHI, MBI, MT, etc. are expected to change.

[0069] A preferred method for producing the branched polypropylene resin (X) used in the present invention is, but is not limited to, the following method. In the method for producing the branched polypropylene resin (X) used in the present invention, from the viewpoint of easily satisfying the above-mentioned characteristics, it is preferable to carry out polymerization using a polymerization catalyst in which two catalyst components, component [A-1] and component [A-2], which generate a macromonomer, are used and the types, amounts and amount ratio of component [A-1] and component [A-2] are selected and combined so that the following conditions are satisfied: a) The molecular weight of the polymer produced from component [A-2] is higher than that of the polymer produced from component [A-1], b) The proportion of terminal vinyl in the polymer produced from component [A-1] is greater than the proportion of terminal vinyl in the polymer produced from component [A-2]; c) Component [A-2] has better copolymerizability with the macromonomer than component [A-1].

[0070] The propylene polymerization catalyst for producing the branched polypropylene resin (X) used in the present invention preferably contains the following components [A-1], [A-2], [B] and [C]. Component [A-1]: a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerized at 70°C; Component [A-2]: A metallocene compound which, when propylene homopolymerized at 70°C, gives a propylene homopolymer a-2 having a larger Mn than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and less than 0.5. Component [B]: a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair Component [C]: Organoaluminum compound

[0071] Component [A-1] is a metallocene compound that gives a propylene homopolymer a-1 with an Rv of 0.5 or more when propylene homopolymerization is performed at 70°C. Component [A-1] is a metallocene compound with an Rv of preferably 0.65 or more, more preferably 0.75 or more, and ideally 1.0 (one end of all molecular chains is a vinyl structure). By using a metallocene compound that forms a polymerization catalyst that produces a propylene homopolymer with a higher Rv, a more efficient macromonomer synthesis process can be performed. Here, the terminal vinyl ratio (Rv) and the terminal vinylidene ratio (Rvd) are defined by the following formulas. Rv = [Vi] / {(total number of terminals - number of LCBs)÷2} Rvd = [Vd] / {(total number of terminals - number of LCBs)÷2} (However, [Vi] and [Vd] are 1 The number of terminal vinyl groups and the number of terminal vinylidene groups per 1,000 monomers calculated by H-NMR. The total number of terminals is 1 H-NMR and 13 The total number of terminals per 1000 monomers calculated by C-NMR. The number of LCBs is 13 The number of LCBs per 1000 monomers calculated by C-NMR.)

[0072] [Relationship between reaction mechanism and terminal structure], [Evaluation method of terminal vinyl ratio (Rv) and terminal vinylidene ratio (Rvd)], <Calculation method of the number of saturated terminals>, <Calculation method of the number of unsaturated terminals>, <Calculation method of the number of LCBs>, <Calculation method of the total number of terminals>, and <Calculation method of terminal vinyl ratio (Rv)·terminal vinylidene ratio (Rvd)> can refer to the descriptions in paragraphs 0073 to 0080 of International Publication No. 2022 / 209773. In addition, the polymerization conditions of propylene when determining Rv and Rvd of the catalyst component are as follows. After replacing the inside of a 20L autoclave with propylene, 18.7 mL of a heptane solution of triisobutylaluminum (140 mg / mL) is charged, 0.51 NL of hydrogen is introduced, and 5000 g of liquid propylene is introduced. Then, a catalyst containing component [A-1] is pumped in at a mass of 300 mg excluding the prepolymerized polymer to start polymerization, and polymerization is carried out at 70 °C for 1 hour. Finally, unreacted propylene is quickly purged to stop the polymerization and obtain a propylene polymer.

[0073] Examples of component [A-1] include bisindenyl complexes having a bulky heterocyclic group at the 2-position of the indenyl group and an aryl group or a heterocyclic group containing a nitrogen, oxygen, or sulfur atom which may be substituted at the 4-position. Specific examples of component [A-1] can refer to paragraphs 0081 to 0088 of International Publication No. 2022 / 209773.

[0074] Component [A-2] is a metallocene compound that gives a propylene homopolymer a-2 having a larger Mn and an Rv of 0.1 or more and less than 0.5 than the propylene homopolymer a-1 when propylene homopolymerization is carried out at 70 °C.

[0075] Component [A-2] is a metallocene compound for copolymerizing a propylene monomer and a propylene macromonomer and forming a polymerization catalyst for producing a propylene macromonomer. Therefore, the component [A-2] is a metallocene compound having an Rv of 0.1 or more, preferably 0.15 or more, and more preferably 0.2 or more. On the other hand, as the component [A-2], a metallocene compound that has a high molecular weight and a low Rv but forms a polymerization catalyst that efficiently copolymerizes a macromonomer is used, thereby making it possible to suppress the generation of high molecular weight branched components with long branches. Therefore, the component [A-2] is a metallocene compound having an Rv of less than 0.5, preferably 0.45 or less, and more preferably 0.3 or less.

[0076] Furthermore, in order to obtain the average molecular weight, molecular weight distribution and branching distribution, which are the characteristics of the branched polypropylene resin (X) used in the present invention, such that Mw, Mz and g' (1 million) have the above-mentioned properties, and preferably W2 million / W1 million satisfies the above-mentioned properties, it is necessary for component [A-2] to produce a polymer having a higher molecular weight than component [A-1]. Therefore, component [A-2] is a metallocene compound that produces a higher molecular weight polymer than component [A-1] when propylene homopolymerization is performed at 70°C with the same amount of hydrogen.

[0077] In order to obtain an average molecular weight, molecular weight distribution and branching distribution such that the branched polypropylene resin (X) used in the present invention satisfies the above-mentioned properties, it is preferable that the component [A-2] has a better copolymerizability of the macromonomer than the component [A-1]. Therefore, it is preferable that component [A-2] is a metallocene compound in which, when propylene is homopolymerized at 70°C, the proportion of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is greater than that of component [A-1].

[0078] By selecting the component [A-2] as described above, it is possible to preferentially cause the reaction in which the macromonomer with a relatively small molecular weight produced in the component [A-1] is copolymerized with the component [A-2]. The evaluation method for Rv and Rvd is the same as that for component [A-1], except that 100 mg of a catalyst containing component [A-2] (excluding the prepolymerized polymer) is used and 1.19 NL of hydrogen is introduced to polymerize. In addition, the Mw characteristics can be evaluated in the same manner as in the evaluation of Rv and Rvd, by performing bulk polymerization at 70°C, measuring the polymers produced from component [A-2] and component [A-1] by GPC, and comparing the Mw values ​​obtained. Furthermore, the copolymerization characteristics of the macromonomer can be evaluated by performing bulk polymerization at 70°C in the same manner as in the evaluation of Rv and Rvd, and comparing the proportion of the number of terminal vinyls produced that have copolymerized into LCBs {LCB number / ([Vi]+LCB number)} obtained by NMR measurement of the polymer produced from component [A-2] and component [A-1].

[0079] As described above, the ratio of macromonomer in the polymer produced from component [A-2] is lower than that in the polymer produced from component [A-1], so the amount of copolymerization of macromonomer 2 is suppressed. On the other hand, since macromonomer copolymerization is better than that of component [A-1], the branch chain length can be adjusted in the introduced branch structure of branched polypropylene resin (X) by efficiently copolymerizing macromonomer 1. By utilizing this branch chain length adjustment, it is possible to obtain a branched polypropylene resin (X) having the average molecular weight, molecular weight distribution and branch distribution, branch structure, and melt properties (Ea, etc.) resulting therefrom, such that Mw, Mz, and g' (1 million), which are the characteristics of the branched polypropylene resin (X) used in the present invention, satisfy the above-mentioned properties.

[0080] The component [A-2] may be, for example, a metallocene compound of formula (I) described in JP-A-2007-528925. In particular, the component [A-2] may be a metallocene compound of formula (IV) described in JP-A-2007-528925.

[0081] Specific examples of the metallocene compound of formula (IV) described in JP-A-2007-528925 are shown below, but the invention is not limited thereto. Dimethylsilylenebis(cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(5-methyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,3,5-trimethyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(4-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(2,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-dimethylphenyl)-cyclopenta[b]thienyl)hafnium dichloride Dimethylsilylenebis(2,5-dimethyl-3-(3,5-di-t-butylphenyl)-cyclopenta[b]thienyl)hafnium dichloride

[0082] Other examples include compounds in which one or both of the dichlorides in the above-listed compounds are replaced with a bromine atom, an iodine atom, a methyl group, a phenyl group, a dimethylamino group, a diethylamino group, etc. In addition, when an asymmetric carbon is generated in these metallocene compounds, one of the stereoisomers or a mixture thereof (including a racemic mixture) is shown unless otherwise specified.

[0083] As a synthesis method for the metallocene complex represented by the general formula [a2], a conventionally known synthesis method can be appropriately selected and used. For example, the synthesis can be performed by referring to JP-T-2007-528925 and JP-A-2021-152155.

[0084] Component [B] is a compound or layered silicate that reacts with component [A-1] and component [A-2] to form an ion pair. Component [B] may be used alone or in combination of two or more thereof. Component [B] is preferably a layered silicate. As the component [B], a conventionally known component can be appropriately selected and used. For specific examples of the component [B], reference can be made to paragraphs 0103 to 0111 of International Publication No. WO 2022 / 209773.

[0085] The component [C] used in the present invention is an organoaluminum compound, and a conventionally known one can be appropriately selected and used. For the component [C], reference can be made to paragraph 0112 of International Publication No. WO 2022 / 209773.

[0086] In addition, the preparation of the olefin polymerization catalyst preferably used in the present invention can be appropriately selected and used according to a conventionally known method, for example, by referring to paragraphs 0113 to 0116 of International Publication No. 2022 / 209773.

[0087] In addition, the polymerization method of the branched polypropylene resin (X) used in the present invention includes a method of homopolymerizing propylene or copolymerizing propylene and a comonomer in the presence of a propylene polymerization catalyst containing components [A-1], [A-2], [B] and [C]. As a specific polymerization method, a conventionally known method can be appropriately selected and used, and for example, paragraphs 0117 to 0123 of WO2022 / 209773 can be referred to.

[0088] The branched polypropylene resin (X) used in the present invention may be in the form of powder, particles, etc. Here, the particulate branched polypropylene resin (X) includes granulated products of the branched polypropylene resin (X).

[0089] When additives are mixed with the branched polypropylene resin (X), a Henschel mixer, a V blender, a ribbon blender, a kneader and / or a tumbler blender, etc. can be used. For the production of granules, a kneader such as a single screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer can be used.

[0090] 2. Polypropylene resin (Y) The polypropylene-based resin (Y) used in the present invention may be a homopolymer of propylene, or a copolymer of propylene and one or more comonomers selected from α-olefin comonomers having 2 to 20 carbon atoms other than propylene, such as ethylene, 1-butene, 1-hexene, 1-octene, 4-methyl-1-pentene, etc. However, the polypropylene-based resin (Y) used in the present invention is different from the branched polypropylene-based resin (X). The polypropylene-based resin (Y) used in the present invention may be a propylene-based polymer comprising propylene, ethylene, and 0 to 11 mol % of an α-olefin having 4 or more carbon atoms. The polypropylene-based resin (Y) used in the present invention is preferably a propylene homopolymer from the viewpoint of increasing the strength of the film.

[0091] 2-1. Characteristics of polypropylene resin (Y) Characteristics (Y-1): The polypropylene resin (Y) used in the present invention has a melt flow rate (MFR) measured at a temperature of 230° C. and a load of 2.16 kg of 0.1 g / 10 min or more and less than 10 g / 10 min from the viewpoints of processability in a cast method of the polypropylene resin composition and transparency and strength of the film. The MFR (230° C., load 2.16 kgf) of the polypropylene resin (Y) is preferably 0.1 g / 10 min to 8 g / 10 min, more preferably 0.1 g / 10 min to 6 g / 10 min.

[0092] The MFR of the polypropylene resin (Y) can be adjusted by changing the temperature conditions during propylene polymerization, changing the pressure conditions during propylene polymerization, and / or changing the method of adding a chain transfer agent such as hydrogen during polymerization.

[0093] Characteristics (Y-2): In the polypropylene-based resin (Y) used in the present invention, from the viewpoint of transparency and strength of the unstretched film, the melting point (Tm) measured by differential scanning calorimetry is preferably 140°C to 180°C, more preferably 150°C to 170°C, and even more preferably 160°C to 170°C. In the present invention, the melting point (Tm) can be determined by using a DSC (DSC6200) manufactured by Seiko Instruments Inc., packing 5 mg of pellet-shaped sample pieces into an aluminum pan, heating from room temperature to 200°C at a heating rate of 100°C / min, holding at 200°C for 5 minutes, and then cooling from 200°C to 40°C at a heating rate of 10°C / min to crystallize the sample, determining the maximum crystallization peak temperature (°C) as the crystallization temperature (Tc), and then heating from 40°C to 200°C at a heating rate of 10°C / min to melt the sample, determining the maximum melting peak temperature (°C) as the melting point (Tm). The pellet-shaped sample can be obtained by melt-kneading the resin using a granulator, withdrawing the molten resin extruded from a strand die while cooling and fixing it in a cooling water tank, and cutting the strands using a strand cutter.

[0094] The melting point (Tm) is adjusted by the content of comonomers other than propylene monomer during propylene polymerization. The more propylene monomer is added, the higher the melting point (Tm), with propylene homopolymer having the highest melting point. On the other hand, the more the content of comonomers other than propylene is added, the lower the melting point (Tm). Therefore, the melting point (Tm) of the polypropylene resin (Y) can be adjusted by adjusting the content of comonomers other than propylene monomer.

[0095] 2-2. Manufacturing method of polypropylene resin (Y) The polymerization catalyst for producing the polypropylene resin (Y) may be a Ziegler-Natta catalyst and / or a metallocene catalyst, but may also be another catalyst. Ziegler-Natta catalysts are described in Section 2.3.1 (pages 20-57) of "Polypropylene Handbook," edited by Edward P. Moore Jr., translated and supervised by Yasuda Tetsuo and Sakuma Nobuo, Kogyo Chosakai (1998). Ziegler-Natta catalysts include (1) titanium trichloride catalysts consisting of titanium trichloride and organoaluminum halide, magnesium chloride, titanium halide, (2) magnesium-supported catalysts consisting of solid catalyst components containing electron donor compounds, organoaluminum and organosilicon compounds, and (3) catalysts combining organoaluminum compound components with organosilicon-treated solid catalyst components formed by contacting solid catalyst components with organoaluminum and organosilicon compounds.

[0096] The metallocene catalyst includes a catalyst in combination with (i) a metallocene compound, (ii) a co-catalyst capable of being activated to a stable ionic state by reacting with the metallocene compound, and (iii) an organoaluminum compound. In order to improve the mechanical properties of the polypropylene resin (Y), the metallocene compound used to synthesize the polypropylene resin (Y) is preferably a crosslinked metallocene compound capable of stereoregular polymerization of propylene, and more preferably a crosslinked metallocene compound capable of isoregular polymerization of propylene.

[0097] Examples of the metallocene compound (i) include those described in JP-A-60-35007, JP-A-61-130314, JP-A-63-295607, JP-A-1-275609, JP-A-2-41303, JP-A-2-131488, JP-A-2-76887, JP-A-3-163088, JP-A-4-300887, JP-A-4-211694, JP-A-5-43616, JP-A-5-209013, JP-A-6-239914, JP-T-H7-504934 and JP-A-8-85708.

[0098] Specific examples of the metallocene compound (i) include: Methylenebis(2-methylindenyl)zirconium dichloride, Ethylenebis(2-methylindenyl)zirconium dichloride, Ethylene 1,2-(4-phenylindenyl)(2-methyl-4-phenyl-4H-azulenyl)zirconium dichloride, Isopropylidene(cyclopentadienyl)(fluorenyl)zirconium dichloride, isopropylidene(4-methylcyclopentadienyl)(3-t-butylindenyl)zirconium dichloride, Dimethylsilylene(2-methyl-4-t-butyl-cyclopentadienyl)(3'-t-butyl-5'-methyl-cyclopentadienyl)zirconium dichloride, Dimethylsilylenebis(indenyl)zirconium dichloride, Dimethylsilylenebis(4,5,6,7-tetrahydroindenyl)zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride, Dimethylsilylenebis[4-(1-phenyl-3-methylindenyl)]zirconium dichloride, Dimethylsilylene(fluorenyl) t-butylamido zirconium dichloride, Methylphenylsilylenebis[1-(2-methyl-4-(1-naphthyl)-indenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4,5-benzoindenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-methyl-4-phenyl-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-naphthyl-4H-azulenyl)]zirconium dichloride, Diphenylsilylenebis[1-(2-methyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, Dimethylsilylenebis[1-(2-ethyl-4-(3-fluorobiphenylyl)-4H-azulenyl)]zirconium dichloride, Dimethylgermylenebis[1-(2-ethyl-4-(4-chlorophenyl)-4H-azulenyl)]zirconium dichloride, and Dimethylgermylenebis[1-(2-ethyl-4-phenylindenyl)]zirconium dichloride and the like zirconium compounds.

[0099] The metallocene compound (i) in which the zirconium is replaced with titanium or hafnium, and / or a mixture thereof, can also be used as a polymerization catalyst for producing a polypropylene resin (Y). The metallocene compound (i) in which the chloride is replaced with other halogen compounds, hydrocarbon groups such as methyl, isobutyl, and benzyl, amide groups such as dimethylamide and diethylamide, alkoxide groups such as methoxy and phenoxy, and hydride groups can also be used as a polymerization catalyst for producing a polypropylene resin (Y).

[0100] In order to improve the moldability of a resin composition containing a polypropylene-based resin (Y), the metallocene compound (i) which is a polymerization catalyst for producing the polypropylene-based resin (Y) is preferably a metallocene compound in which an indenyl group or an azulenyl group is crosslinked with a silicon or germyl group.

[0101] The polymerization catalyst for producing the polypropylene-based resin (Y) may be supported on an inorganic or organic compound. In order to improve the production amount of the polypropylene-based resin (Y), the support is preferably porous. The support is preferably an inorganic compound such as ion-exchangeable layered silicate, zeolite, SiO2, Al2O3, silica alumina, MgO, ZrO2, TiO2, B2O3, CaO, ZnO, BaO, ThO2, etc., an organic compound such as porous polyolefin, styrene-divinylbenzene copolymer, olefin-acrylic acid copolymer, etc., or a mixture thereof.

[0102] In order to improve the production amount of the polypropylene resin (Y), it is preferable to use a co-catalyst together with the metallocene compound. The co-catalyst is preferably an organoaluminum oxy-compound such as an aluminoxane compound, an ion-exchangeable layered silicate, a Lewis acid, a boron-containing compound, an ionic compound, or a fluorine-containing organic compound.

[0103] In order to improve the productivity of the polypropylene resin (Y), the organoaluminum compound (iii) is preferably a trialkylaluminum such as trimethylaluminum, triethylaluminum, triisopropylaluminum, triisobutylaluminum or trioctylaluminum, a dialkylaluminum halide, an alkylaluminum sesquihalide, an alkylaluminum dihalide, diethylaluminum chloride, ethylaluminum chloride, diethylaluminum ethoxide, methylalumoxane, an alkylaluminum hydride or an organoaluminum alkoxide.

[0104] In order to improve the production efficiency of the polypropylene resin, the production method of the polypropylene resin (Y) is preferably a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. For the production of polypropylene and propylene random copolymers, a multi-stage polymerization method such as a slurry polymerization method, a bulk polymerization method, a gas phase polymerization method, etc. can be used.

[0105] When additives are mixed with the polypropylene-based resin (Y), the polypropylene-based resin (Y) may be produced by mixing together with necessary additives using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender, etc. The polypropylene-based resin (Y) may be produced by kneading using a kneading machine such as a single-screw extruder, a multi-screw extruder, a kneader, or a Banbury mixer.

[0106] The polypropylene resin (Y) may be in the form of a powder, particles, etc. The particles of the polypropylene resin (Y) include granulated products of the polypropylene resin (Y).

[0107] 3. Polypropylene resin composition The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing a branched polypropylene resin (X) and a polypropylene resin (Y) in a specific ratio described in detail below. From the viewpoint of transparency of the non-stretched film, the polypropylene resin composition of the present invention contains a branched polypropylene resin (X) in an amount of 1% by mass to 95% by mass relative to 100% by mass of the total mass of the resin (X) and the resin (Y). The content of the branched polypropylene resin (X) may be 5% by mass or more, 10% by mass or more, 30% by mass or more, or 50% by mass or more relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may be 90% by mass or less, 80% by mass or less, or 70% by mass or less. From the viewpoint of transparency of the non-stretched film, the polypropylene resin composition of the present invention contains 5% by mass to 99% by mass of polypropylene resin (Y) relative to 100% by mass of the total mass of the resin (X) and the resin (Y). The content of polypropylene resin (Y) may be 10% by mass or more, 20% by mass or more, or 30% by mass or more relative to 100% by mass of the total mass of the resin (X) and the resin (Y), and may be 95% by mass or less, 90% by mass or less, 70% by mass or less, or 50% by mass or less.

[0108] The polypropylene resin composition of the present invention is a branched polypropylene resin composition containing the branched polypropylene resin (X) and the polypropylene resin (Y) as essential components, and may further contain other components such as additives and other polymers different from the branched polypropylene resin (X) and the polypropylene resin (Y).

[0109] 3-1.Additives The polypropylene resin composition of the present invention may further contain additives as necessary in addition to the branched polypropylene resin (X) and polypropylene resin (Y). By appropriately selecting the additives, the functions of the polypropylene resin composition can be improved. The additives may be used alone or in combination of two or more. The additives include, for example, at least one selected from the group consisting of antioxidants, lubricants, antistatic agents, antiblocking agents, UV absorbers, light stabilizers, and neutralizing agents.

[0110] Examples of the antioxidant include phenol-based stabilizers such as 2,6-di-t-butyl-p-cresol, tetrakis[methylene-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate]methane and n-octadecyl-3-(4'-hydroxy-3,5'-di-t-butylphenyl)propionate, and phosphite-based stabilizers such as bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite and tris(2,4-di-t-butylphenyl)phosphite. Examples of the lubricant include higher fatty acid amides and higher fatty acid esters. Examples of the antistatic agent include glycerin esters, sorbitan acid esters, and polyethylene glycol esters of fatty acids having 8 to 22 carbon atoms. Examples of anti-blocking agents include silica, calcium carbonate, and talc.

[0111] Furthermore, by incorporating an ultraviolet absorber and a light stabilizer in the polypropylene resin composition, the weather resistance of the polypropylene resin composition can be improved. Examples of the ultraviolet absorbent include compounds having an absorption band in the ultraviolet region, such as triazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, salicylate-based ultraviolet absorbents, cyanoacrylate-based ultraviolet absorbents, nickel chelate-based ultraviolet absorbents, inorganic fine particle-based ultraviolet absorbents, etc. Among these, triazole-based ultraviolet absorbents are a typical example. Examples of triazole-based ultraviolet absorbers include 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-5'-t-octylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-butylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t-amylphenyl)benzotriazole, and 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)-5-chlorobenzotriazole. Benzophenone-based ultraviolet absorbents include, for example, 2-hydroxy-4-methoxybenzophenone, 2-hydroxy-4-n-octoxybenzophenone, and the like. An example of the salicylate-based ultraviolet absorber is 4-t-butylphenyl salicylate. An example of a cyanoacrylate-based ultraviolet absorber is ethyl (3,3-diphenyl) cyanoacrylate. An example of the nickel chelate ultraviolet absorber is nickel dibutyldithiocarbamate. Examples of inorganic particulate ultraviolet absorbents include TiO2, ZnO2, and CeO2.

[0112] Typical light stabilizers include compounds having a hindered amine skeleton (hereinafter referred to as "HALS"). HALS includes sebacate type compounds, butanetetracarboxylate type compounds, succinic acid polyester type compounds, triazine type compounds, and the like. Examples of the sebacate type compound include bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, and the like. Examples of butane tetracarboxylate type compounds include tetrakis(2,2,6,6-tetramethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl)-1,2,3,4-butane tetracarboxylate, a condensate of 1,2,3,4-butane tetracarboxylic acid with 2,2,6,6-tetramethyl-4-piperidinol and tridecyl alcohol, and a condensate of 1,2,3,4-butane tetracarboxylic acid with 1,2,2,6,6-pentamethyl-4-piperidinol and tridecyl alcohol. An example of the succinic acid polyester type compound is a condensation polymer of succinic acid and 1-(2-hydroxyethyl)-4-hydroxy-2,2,6,6-tetramethylpiperidine. Examples of triazine-type compounds include N,N'-bis(3-aminopropyl)ethylenediamine·2,4-bis{N-butyl-N-(1,2,2,6,6-pentamethyl-4-piperidyl)amino}-6-chloro-1,3,5-triazine condensate, poly{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino, and poly(6-morpholino-s-triazine-2,4-diyl){(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino.

[0113] In the polypropylene resin composition of the present invention, the total content of the additives is not particularly limited as long as it is appropriately selected according to the properties of the additives. In the polypropylene resin composition of the present invention, the upper limit of the total content of the additives may be, for example, 10 parts by mass or less, 1 part by mass or less, or 0.5 parts by mass or less, and the lower limit may be 0 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the polypropylene resin (Y).

[0114] 3-2.Other polymers The polypropylene resin composition of the present invention may further contain other polymers as necessary in addition to the above-mentioned branched polypropylene resin (X) and polypropylene resin (Y). The other polymers can improve the performance or adjust the properties of the branched polypropylene resin composition as modifiers in the polypropylene resin composition. Examples of the other polymers used as modifiers include, but are not limited to, elastomers, polyethylene resins, etc. Examples of the elastomer include ethylene-α-olefin copolymers, binary random copolymer resins of propylene and an α-olefin having 4 to 12 carbon atoms, and ternary random copolymer resins of propylene, ethylene, and an α-olefin having 4 to 12 carbon atoms. Examples of styrene-based elastomers include hydrogenated styrene-butadiene block copolymers, hydrogenated styrene-isoprene block copolymers, hydrogenated styrene-vinylated polyisoprene block copolymers, and hydrogenated styrene-butadiene random copolymers.

[0115] Examples of polyethylene resins include ethylene / α-olefin copolymers such as low-density polyethylene and linear low-density polyethylene, and their density is 0.860 g / cm. 3 ~0.910g / cm 3 and preferably in the range of 0.870 g / cm 3 ~0.905g / cm 3 More preferably, it is 0.875 g / cm 3 ~0.895g / cm 3 If the content exceeds the above range, the transparency may decrease. The density is a value measured at 23° C. in accordance with JIS K7112. The α-olefin used in the ethylene / α-olefin copolymer is preferably an α-olefin having 3 to 18 carbon atoms. Specific examples include propylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-heptene, 4-methyl-pentene-1, 4-methyl-hexene-1, 4,4-dimethylpentene-1, etc. The α-olefin may be one type or a combination of two or more types. Examples of such ethylene / α-olefin copolymers include ethylene-based elastomers, ethylene-propylene-based rubbers, etc. In particular, ethylene / α-olefin copolymers called metallocene-based polyethylenes, which are produced using metallocene-based catalysts with little loss of transparency, are preferred.

[0116] In the polypropylene resin composition of the present invention, the total content of the other polymers is not particularly limited as long as the effect is not impaired and may be appropriately selected according to the purpose. The upper limit of the total content of the other polymers may be, for example, 50 parts by mass or less, 30 parts by mass or less, or 10 parts by mass or less, and the lower limit may be 0 parts by mass, but may be 1 part by mass or more, or 3 parts by mass or more, relative to 100 parts by mass of the total of the branched polypropylene resin (X) and the polypropylene resin (Y).

[0117] The polypropylene resin composition of the present invention is prepared by blending 100 parts by mass of the branched polypropylene resin (X) and the polypropylene resin (Y) in total, or other components that do not impair the effects of the present invention, as required. Examples of the method for mixing these components include a method of mixing using a Henschel mixer, V blender, ribbon blender, tumbler blender, etc., and a method of melt-kneading using a kneader such as a single-screw extruder, multi-screw extruder, kneader, or Banbury mixer, as required. In either case, there is no particular limitation on the mixing method as long as the effects of the present invention are not impaired.

[0118] 4. Characteristics of polypropylene resin composition The polypropylene resin composition of the present invention may have a melt flow rate (MFR) measured at a temperature of 230°C under a load of 2.16 kg of 1 g / 10 min to 50 g / 10 min, preferably 2 g / 10 min to 30 g / 10 min, and more preferably 3 g / 10 min to 15 g / 10 min, from the viewpoints of processability in a casting method of the polypropylene resin composition and transparency and strength of the film.

[0119] In the polypropylene resin composition of the present invention, from the viewpoints of transparency and strength of the unstretched film, the melting point (Tm) measured by differential scanning calorimetry is preferably 140°C to 180°C, more preferably 150°C to 170°C, and even more preferably 160°C to 170°C. In the polypropylene resin composition of the present invention, from the viewpoints of transparency and strength of the unstretched film, the crystallization temperature (Tc) measured by differential scanning calorimetry is preferably 100°C to 140°C, more preferably 110°C to 130°C, and even more preferably 120°C to 130°C.

[0120] From the viewpoint of increasing strength, the polypropylene resin composition of the present invention may have a melt tension at 230° C. (MT230) of 0.1 g to 5 g, or 0.3 g to 4 g.

[0121] 5. Uses of polypropylene resin compositions The polypropylene resin composition of the present invention can be used for producing various molded articles by appropriately molding into a desired shape by means of pressure molding, film molding, vacuum molding, extrusion molding, extrusion lamination molding, foam molding, blow molding, injection molding, or the like. The polypropylene resin composition of the present invention can be suitably used for non-stretched films, in particular. That is, one aspect of the polypropylene resin composition of the present invention is a branched polypropylene resin composition for non-stretched films.

[0122] 6. Method for producing polypropylene resin composition The polypropylene resin composition of the present invention can be produced by blending, mixing, and melt-kneading the branched polypropylene resin (X), the polypropylene resin (Y), and the additives used as necessary in the above-mentioned content ratios by a conventionally known method.

[0123] The polypropylene resin composition of the present invention can be mixed by dry blending using a Henschel mixer, a V blender, a ribbon blender, a tumbler blender or the like. In addition, when producing the composition by melt-kneading and granulation, the above-mentioned mixture of components may be kneaded at the same time. Furthermore, in order to improve the performance, each component may be divided and kneaded separately, that is, for example, a method may be adopted in which a part of the components to be used is first kneaded, and then the remaining components are kneaded and granulated.

[0124] The polypropylene resin composition of the present invention is preferably produced by dry blending the components to be used. As a preferred embodiment of the method for producing a polypropylene-based resin composition of the present invention, a branched polypropylene-based resin (X) having the above-mentioned properties (X-1) to (X-4) and and a polypropylene resin (Y) having the above-mentioned characteristic (Y-1). By mixing the branched polypropylene resin (X) and the polypropylene resin (Y) by dry blending, it is possible to uniformly mix them in a relatively short time at low cost, and stable performance can be obtained. The resulting mixture is usually melt-kneaded as described above.

[0125] II. Method for producing polypropylene resin film The method for producing a polypropylene-based resin film of the present invention includes a step of forming a film from the polypropylene-based resin composition of the present invention by a cast film formation method. The polypropylene resin film according to the present invention obtained by forming the film by the cast film forming method may be a non-stretched film made of the polypropylene resin composition of the present invention.

[0126] The production of a non-oriented film by the cast film production method is preferably carried out by melting the polypropylene resin composition of the present invention using an extruder equipped with a T-die to form a sheet, extruding the sheet, blowing air supplied from a blower or the like onto the sheet to bring it into close contact with a chill roll, cooling and solidifying the sheet, and then taking it up with a take-up machine.

[0127] The die diameter is typically φ50 mm to φ500 mm, and the die lip width is typically 0.8 mm to 4.0 mm. From the viewpoints of design such as film transparency and productivity such as stable continuous film production, the film production temperature is preferably 170°C to 250°C, and more preferably 170°C to 230°C. In order to improve the uniformity of the film, such as by suppressing fluttering of the film, the forming speed is preferably 5 m / min to 300 m / min, and more preferably 10 m / min to 250 m / min.

[0128] The thickness of the formed film is not particularly limited and may be appropriately selected depending on the application. The thickness of the film is usually 1 μm to 250 μm, may be 3 μm to 200 μm, or may be 5 μm to 150 μm.

[0129] The film of the present invention has excellent optical properties, and the total haze is preferably 10% or less, and more preferably 9.5% or less. The smaller the total haze value (unit: %), the more excellent the transparency. In the present invention, the total haze is measured in accordance with JIS K7105.

[0130] The film of the present invention has excellent optical properties, and the internal haze is preferably 1.5% or less, and more preferably 1% or less. The smaller the internal haze value (unit: %), the more excellent the transparency. In the present invention, the internal haze is measured in accordance with JIS K7136:2000, in which oil is poured between two standard glass pieces, a film is inserted between them, and the internal haze value of the film is measured. The oil used is liquid paraffin.

[0131] Furthermore, the film of the present invention has excellent strength, and the Young's modulus in both the direction horizontal to the film-forming direction (MD) and the direction perpendicular to the film-forming direction (TD) is preferably 1100 MPa or more, more preferably 1200 MPa or more. In the present invention, Young's modulus is measured in accordance with JIS K7127: 1999. The higher the Young's modulus value, the higher the strength.

[0132] Furthermore, the film of the present invention has excellent straight-line cutting properties, and the tear strength in both the direction horizontal to the film-forming direction (MD) and the direction perpendicular to the film-forming direction (TD) is preferably 3 N / mm or less, more preferably 2 N / mm or less. In the present invention, the tear strength is measured by the Elmendorf tear method in accordance with JIS K7128-2: 1998. The smaller the tear strength value, the easier it is to tear. EXAMPLES

[0133] Next, the present invention will be described more specifically with reference to examples. However, the present invention is not limited to the following examples as long as it does not depart from the gist of the present invention. In the following examples, the autoclave was thoroughly dried in advance by passing nitrogen through it under heating before use, and the catalyst preparation and polymerization were all carried out under an inert gas. In the present embodiment, the term "MD" refers to the direction in which the film is fed during extrusion molding, and the term "TD" refers to the direction perpendicular to the direction in which the film is fed during extrusion molding and parallel to the film surface.

[0134] I. Measurement and Evaluation Methods The following (1) to (17) were measured and calculated by the methods described in this specification. (1) MFR Furthermore, the measured MFR value was used to calculate the right-hand sides of the above formulas (1), (2) and (7). (2) Mw / Mn and Mz / Mw obtained by GPC (3) W1 million, W2 million, and W2 million / W1 million in the integral molecular weight distribution curve obtained by GPC (4) g' (million), g' (Mw abs ), and [g'(Mw abs )-g'(1 million)] (5) Ea in dynamic viscoelasticity measurement (6) 13 mm, [2,1 bond] amount, and [1,3 bond] amount measured by C-NMR (7) 13 LCB number measured by C-NMR (8) SHI@1.0s obtained from extensional viscosity measurement -1 and MBI (9) Melt tension (MT230) (10) MaxDraw (11) [Vi], terminal vinyl ratio, number of LCBs / ([Vi]+number of LCBs) (12) Melting point (Tm)

[0135] (13) Internal haze (unit: %) (14) Total Haze (unit: %) (15)Young’s modulus The Young's modulus of the film in the MD direction is referred to as "Young's modulus (MD)" and the Young's modulus of the film in the TD direction is referred to as "Young's modulus (TD)". (16) Tear strength The tear strength of the film in the MD direction is referred to as "tear strength (MD)" and the tear strength of the film in the TD direction is referred to as "tear strength (TD)".

[0136] (17) Straight cutting ability The film is evaluated for its straightness and tear resistance when torn in the MD direction. A 5mm cut was made along the MD of the edge of the film. A force was applied from this cut in the direction of 0° to the TD and 180° to the MD, and the film was torn 30cm. The straightness and tear resistance were evaluated when the film was torn. If the cut was straight and not disturbed, and the film could be torn without resistance, the straightness of the film was said to be high. (Evaluation Criteria) - If the cut is smooth and there is no resistance, and it can be torn to 30cm, it is given a "Excellent" rating. - If the cut is slightly irregular and there is a slight resistance, but you can tear it to 30cm, give it a "good" mark. - The cut is slightly irregular and there is some resistance, but it can be torn to 30cm, so it is rated as "△". - If the cut was irregular, there was resistance, and it could not be torn to 30 cm, mark it as "X".

[0137] II. Production of polypropylene resin composition and film 1. Branched polypropylene resin (X) 1-1. Production of branched polypropylene resin (X1) (1) Synthesis of catalyst component (A) (1-1) Synthesis Example 1: Synthesis of catalyst component [A-1] (Complex 1) Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium: rac-Dichloro[1,1′-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium was synthesized according to the method of Synthesis Example 1 in JP2012-149160A.

[0138] (1-2) Synthesis Example 2: Synthesis of catalyst component [A-2] (Complex 2) 1) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2): (1-a) Synthesis of 2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene: The synthesis was carried out with reference to the method described in Example 1 of JP-A-2003-517010. (1-b) Synthesis of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane: 2,5-Dimethyl-3-phenyl-hydrocyclopenta[b]thiophene (8.8g, 39mmol) and THF (200ml) were added to a 500ml glass reaction vessel and cooled to -70℃. n-Butyllithium-n-hexane solution (1.55mol / L, 25ml, 39mmol) was added dropwise. After the addition, the mixture was stirred for 2 hours while gradually returning to room temperature. The mixture was cooled again to -70℃, 1-methylimidazole (0.15ml, 1.9mmol) was added, and a THF solution (30ml) containing dimethyldichlorosilane (2.5g, 19mmol) was added dropwise. After the addition, the mixture was stirred overnight while gradually returning to room temperature. Distilled water was added to the reaction solution obtained, which was then transferred to a separatory funnel and washed with saline until neutral. Sodium sulfate was added and the reaction solution was left overnight to dry. The sodium sulfate was filtered off, the solvent was removed under reduced pressure, and the resulting solid was purified using a silica gel column to obtain a white powder of dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (9.8 g, 99% yield). (1-c) Synthesis of rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex A): Dimethylbis(2,5-dimethyl-3-phenyl-hydrocyclopenta[b]thiophene)silane (6.1g, 12mmol) and 200ml of diethyl ether were added to a 500ml glass reaction vessel, and the vessel was cooled to -70℃ in a dry ice-methanol bath. A n-butyllithium-n-hexane solution (1.55mol / L, 16ml, 24mmol) was added dropwise to the vessel. After the addition, the mixture was returned to room temperature and stirred for 2 hours. The solvent of the reaction solution obtained was concentrated under reduced pressure to about 20ml, after which 250ml of toluene and 10ml of THF were added, and the mixture was cooled to -70℃ in a dry ice-methanol bath. 3.8g (12mmol) of hafnium tetrachloride was added to the vessel. The mixture was then gradually returned to room temperature and stirred overnight. The solvent was distilled off under reduced pressure and the resulting solid was recrystallized from toluene / hexane to obtain 0.87 g (yield 10%) of racemic dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (purity 97%) as yellow crystals.

[0139] The racemic mixture was analyzed by proton nuclear magnetic resonance ( 1 The identified values ​​by H-NMR are shown below. 1 H-NMR (CDCl3) Identification Results Racemic: δ1.06(s,6H), δ2.42(s,6H), δ2.59(s,6H), δ8.51(s,2H), δ7.28~δ7.33(m,2H), δ7.39~δ7.43(m,4H), δ7.46~δ7.50(m,4H)

[0140] (2) Synthesis example of component (B): Chemical treatment of ion-exchangeable layered silicate Into a 1 L three-neck flask equipped with a stirring blade and a reflux device, 645.1 g of distilled water and 82.6 g of 98% sulfuric acid were added and heated to 95°C. 100 g of commercially available montmorillonite (Benclay KK manufactured by Mizusawa Chemical Industry Co., Ltd., Al=9.78% by mass, Si=31.79% by mass, Mg=3.18% by mass, Al / Si (molar ratio)=0.320, average particle size 14 μm) was added thereto, and the mixture was reacted for 320 minutes at 95° C. After 320 minutes, 0.5 L of distilled water was added to stop the reaction, and 255 g of a cake-like solid was obtained by filtration. This cake (1 g) contained 0.31 g of the chemically treated montmorillonite (intermediate). The chemical composition of the chemically treated montmorillonite (intermediate) was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, and Al / Si (molar ratio) = 0.222. 1545g of distilled water was added to the cake to make a slurry, and the temperature was raised to 40℃. 5.734g of lithium hydroxide hydrate was added as a solid to the slurry, and the reaction was carried out at 40℃ for 1 hour. After 1 hour, the reaction slurry was filtered and washed three times with 1L of distilled water, and a cake-like solid was obtained again. The cake-like solid obtained was pre-dried overnight at 90°C or higher under normal pressure, and then dried under reduced pressure for 2 hours or more after the bumping subsided using an oil bath at 200°C to obtain 80 g of chemically treated montmorillonite. The chemical composition of this chemically treated montmorillonite was Al = 7.68 mass%, Si = 36.05 mass%, Mg = 2.13 mass%, Al / Si (molar ratio) = 0.222, Li = 0.53 mass%.

[0141] (3) Preparation of catalyst 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (45 μmol) prepared in the synthesis example of the catalyst component [A-2] was dissolved in toluene (9 mL) to prepare solution 2.

[0142] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above-mentioned solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Thereafter, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was further added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 28.2 g of a prepolymerized catalyst (Catalyst 1). The prepolymerization ratio (value obtained by dividing the amount of prepolymerized polymer by the amount of solid catalyst) was 1.82.

[0143] (4) Polymerization The 20 L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7 mL of a heptane solution of triisobutylaluminum (140 mg / mL) and 5,000 g of liquid propylene were introduced into the polymerization tank, and the temperature was raised to 63°C. Then, 700 mg of the above catalyst 1 (excluding the prepolymerized polymer) was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature inside the tank was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1,687 g of propylene homopolymer was obtained. The obtained polymer was used for GPC, 3D-GPC, 13 C-NMR measurements were performed.

[0144] (5) Production of branched polypropylene resin pellets (X1) (granulation) 100 parts by mass of the obtained branched polypropylene resin (X) was blended with 0.125 parts by mass of a phenolic antioxidant IRGANOX1010 (manufactured by BASF Japan, tetrakis[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane) and 0.125 parts by mass of a phosphite antioxidant IRGAFOS168 (manufactured by BASF Japan, tris(2,4-di-t-butylphenyl)phosphite) and mixed for 3 minutes at room temperature using a high-speed stirring mixer (Henschel mixer, manufactured by Nippon Coke & Co., Ltd.). Then, using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.), the screw rotation speed was 400 rpm and the kneading temperature was 80, 120, and 230 ° C. from the bottom of the hopper (the same temperature from then until the die outlet). The molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter. The MFR of the obtained pellets was 4.5 g / 10 min. The evaluation results of each property are shown in Table 1.

[0145] 1-2. Production of branched polypropylene resin (X2) Polymerization was carried out in the same manner as in the polymerization for producing the branched polypropylene resin (X1), except that the catalyst 1 was introduced in an amount of 500 mg (excluding the prepolymerized polymer) and 0.09 NL of hydrogen was introduced. As a result, 1750 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 9.0 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0146] 1-3. Production of branched polypropylene resin (X3) Polymerization was carried out in the same manner as in the polymerization for producing the branched polypropylene resin (X1), except that the catalyst 1 was introduced in an amount of 400 mg (excluding the prepolymerized polymer) and 0.43 NL of hydrogen was introduced. As a result, 2109 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 21 g / 10 min. The properties were evaluated in the same manner as in Example 1, and the results are shown in Table 1.

[0147] [Production of Comparative Branched Polypropylene Resin] <Production of Comparative Branched Polypropylene Resin (CX1)> (1) Preparation of catalyst (1-1) Synthesis of comparative catalyst component [CA-2] Synthesis of rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium: rac-Dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) was synthesized according to the method of Example 7 of JP-A-11-240909.

[0148] (1-2) Synthesis example of catalyst 2 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (105 μmol) prepared in the synthesis example of the catalyst component [A-1] was dissolved in toluene (21 mL) to prepare solution 1. Furthermore, in another flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (45 μmol) prepared in the synthesis example of the comparative catalyst component [CA-2] was dissolved in toluene (9 mL) to prepare solution 2.

[0149] Triisobutylaluminum (0.42 mmol: 0.6 mL of a heptane solution with a concentration of 143 mg / mL) was added to a 1 L flask containing the above-mentioned chemically treated montmorillonite, and then the above-mentioned solution 1 (21 mL) was added and stirred at room temperature for 20 minutes. Thereafter, triisobutylaluminum (0.18 mmol: 0.25 mL of a heptane solution with a concentration of 143 mg / mL) was further added, and then the above solution 2 was added, followed by stirring at room temperature for 1 hour. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 30.9% prepolymerized catalyst (catalyst 2). The prepolymerization rate was 2.09%.

[0150] (2) Polymerization and granulation The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) and 0.68NL of hydrogen were introduced into the polymerization tank, followed by 5000g of liquid propylene, and the temperature was raised to 63°C. Then, 310mg of the catalyst 2, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature inside the tank was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 2288g of propylene homopolymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 3.3 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0151] <Production of Comparative Branched Polypropylene Resin (CX2)> Polymerization was carried out in the same manner as in the polymerization for producing a comparative branched polypropylene resin (CX1), except that 230 mg of catalyst 2 (excluding the prepolymerized polymer) and 1.02 NL of hydrogen were introduced. As a result, 1978 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 9.9 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0152] <Production of Comparative Branched Polypropylene Resin (CX3)> Polymerization was carried out in the same manner as in the polymerization for producing a comparative branched polypropylene resin (CX1), except that 220 mg of catalyst 2 (excluding the prepolymerized polymer) and 1.11 NL of hydrogen were introduced. As a result, 1936 g of a polymer was obtained. The polymer obtained above was pelletized in the same manner as in the production of pellets of branched polypropylene resin (X1), and the MFR of the pellets obtained was 15.0 g / 10 min. The results of evaluation of each property are shown in Table 1.

[0153] [Table 1]

[0154] FIG. 2 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents W2 million / W1 million, and data for the branched polypropylene resins (X1) to (X3) used in each example and the comparative branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 4 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents Ea, and data for the branched polypropylene resins (X1) to (X3) used in each example and the comparative branched polypropylene resins (CX1) to (CX3) are plotted. FIG. 5 is a graph in which the horizontal axis represents the logarithm of MFR (log(MFR)) and the vertical axis represents the maximum winding speed (MaxDraw) at 230° C., and data for the branched polypropylene resins (X1) to (X3) used in each example and the comparative branched polypropylene resins (CX1) to (CX3) are plotted.

[0155] 2. Polypropylene resin (Y) As the polypropylene resin (Y), the following polypropylene resins (Y1) to (Y2) were prepared. Polypropylene resin (Y1): Made by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) FL4", MFR = 4 g / 10 min, Tm = 164°C, g' (million) = 1.00 Polypropylene resin (Y2): manufactured by Japan Polypropylene Corporation, trade name "Novatec (registered trademark) SA4L", MFR = 6 g / 10 min, Tm = 161°C, g' (million) = 1.00

[0156] 3. Production of polypropylene resin composition and film production [Examples 1 to 9 and Comparative Examples 1 to 2] (1) Production of polypropylene resin composition Any one of the pellets (X1) to (X3) of the branched polypropylene resin (X) and the pellets (Y1) to (Y2) of the polypropylene resin (Y) in the amounts shown in Table 2 were put into a high-speed stirring mixer and stirred for 3 minutes to obtain mixed pellets. The amounts shown in Table 2 are shown in mass % relative to 100 mass % of the total mass of the resin (X) and the resin (Y). Regarding the pellets used in measuring the MFR of the polypropylene resin composition, the mixed pellets were further melt-kneaded using a twin-screw extruder KZW-15 (manufactured by Technobel Co., Ltd.) at a screw rotation speed of 400 rpm and kneading temperatures of 80, 120, and 230°C (the same temperature from the bottom of the hopper to the die outlet), and the molten resin extruded from the strand die was taken up while being cooled and fixed in a cooling water tank, and the strands were cut and pelletized using a strand cutter.

[0157] [Table 2]

[0158] (2) Manufacturing of non-oriented films The mixed pellets of the polypropylene resin composition obtained above were put into the extruder of a film molding machine, extruded at an extruder temperature of 220°C and a die temperature of 230°C, and then the molten resin was brought into contact with a cooling roll adjusted to 30°C to solidify, while adjusting the discharge amount and take-up speed so that the film width was 300 mm and the thickness was 30 μm. The polypropylene resin composition was extruded under conditions of a total discharge amount of 5 kg / h, and a non-stretched cast film was produced under conditions of a take-up speed of 20 m / min. The physical properties of the obtained non-stretched cast film are shown in Table 3.

[0159] [Table 3]

[0160] From Examples 1 to 9 and Comparative Examples 1 and 2, it was shown that the polypropylene resin composition of the present invention, which contains the branched polypropylene resin (X) having a branched polypropylene structure different from conventional ones, can be molded into a non-oriented film having high strength and excellent optical properties as well as excellent straight cutability.

[0161] The performance evaluation for preparing a catalyst for producing the branched polypropylene resin (X) of the present invention is shown below. [Reference Example 1]: Performance evaluation of complex 1 as catalyst component (A) (Preparation of Catalyst R1) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (65 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 35 mL of heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-(5-methyl-2-furyl)-4-(4-isopropylphenyl)indenyl}]hafnium (complex 1) (0.15 mmol) synthesized in Synthesis Example 1 was dissolved in toluene (30 mL) to prepare a solution.

[0162] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 40 minutes to obtain 29.5 g of a prepolymerized catalyst (Catalyst R1). The prepolymerization rate was 1.95.

[0163] (polymerization) The 20L autoclave was used after replacing the inside of the tank with propylene and cooling to room temperature. 18.7mL of a heptane solution of triisobutylaluminum (140mg / mL) and 0.51NL of hydrogen were introduced into the polymerization tank, followed by 5000g of liquid propylene, and the temperature was raised to 63°C. Then, 300mg of the catalyst R1, excluding the prepolymerized polymer, was pumped into the polymerization tank with high-pressure argon to start polymerization, and the temperature was quickly raised to 70°C. The temperature was kept at 70°C, and after 1 hour from the start of polymerization, the unreacted propylene was quickly purged to stop the polymerization. As a result, 1740g of propylene homopolymer was obtained. Table 2 shows the results of MFR, GPC, and NMR measurements using the obtained polymer.

[0164] [Reference Example 2]: Performance evaluation of complex 2 as catalyst component (A) (Preparation of Catalyst R2) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dimethylsilylenebis(2,5-dimethyl-3-phenyl-cyclopenta[b]thienyl)hafnium dichloride (complex 2) (0.15 mmol) synthesized in Synthesis Example 2 was dissolved in toluene (30 mL) to prepare a solution.

[0165] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was set to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Then, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6 mmol: 8.5 mL of a heptane solution with a concentration of 143 mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 32.0 g of a prepolymerized catalyst (Catalyst R2). The prepolymerization rate was 2.20.

[0166] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R2 was used instead of catalyst R1, 100 mg of the mass excluding the prepolymerized polymer, and 1.19 NL of hydrogen was introduced. As a result, 1153 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 2.

[0167] [Reference Example 3]: Performance evaluation of complex 3 as catalyst component (A) (Preparation of catalyst R3) 10 g of the chemically treated montmorillonite obtained above was placed in a three-neck flask (volume 1 L) and heptane (66 mL) was added to make a slurry. Triisobutylaluminum (25 mmol: 34.0 mL of a heptane solution with a concentration of 143 mg / mL) was added to the slurry and stirred for 1 hour, and then washed with heptane until the residual liquid ratio was 1 / 100, and the total volume was made 50 mL. In addition, in a separate flask (volume 200 mL), rac-dichloro[1,1'-dimethylsilylenebis{2-methyl-4-(4-chlorophenyl)-4-hydroazulenyl}]hafnium (complex 3) (0.15 mmol) synthesized in Synthesis Example 3 was dissolved in toluene (30 mL) to prepare a solution.

[0168] To the 1 L flask containing the above-mentioned chemically treated montmorillonite, triisobutylaluminum (0.60 mmol: 0.85 mL of a heptane solution with a concentration of 143 mg / mL) was added, and then the above solution was added and stirred at room temperature for 60 minutes. Then, 170 mL of heptane was added to the mixture, and the slurry was introduced into a 1 L autoclave. After the internal temperature of the autoclave was brought to 40°C, propylene was fed at a rate of 5g / hour, and prepolymerization was carried out while maintaining 40°C for 4 hours. Thereafter, the propylene feed was stopped, and residual polymerization was carried out for 1 hour. After removing the supernatant of the obtained catalyst slurry by decantation, triisobutylaluminum (6mmol: 8.5mL of heptane solution with a concentration of 143mg / mL) was added to the remaining portion and stirred for 5 minutes. The catalyst slurry was dried under reduced pressure for 1 hour to obtain 31.0 g of a prepolymerized catalyst (Catalyst R3). The prepolymerization rate was 2.10.

[0169] (polymerization) Polymerization was carried out in the same manner as in Reference Example 1, except that catalyst R3 was used instead of catalyst R1, 300 mg of the mass excluding the prepolymerized polymer, and 0.51 NL of hydrogen was introduced. As a result, 1570 g of polymer was obtained. The results of MFR, GPC, and NMR measurements of the obtained polymer are shown in Table 4.

[0170] From the results of Reference Examples 1 to 3 in Table 4, it was shown that complex 1 can be used as a metallocene compound that gives a propylene homopolymer a-1 having a terminal vinyl ratio (Rv) of 0.5 or more when propylene homopolymerization is performed at 70°C using component [A-1], and complex 2 can be used as a metallocene compound that gives a propylene homopolymer a-2 having a number average molecular weight (Mn) larger than that of the propylene homopolymer a-1 and an Rv of 0.1 or more and smaller than 0.5 when propylene homopolymerization is performed at 70°C using component [A-2], and the propylene homopolymer a-2 can be used as a metallocene compound in which the ratio of the number of terminal vinyls produced that are copolymerized into LCBs {LCB number / ([Vi]+LCB number)} is larger than that of the propylene homopolymer a-1. Complex 3 was a metallocene compound that gave a propylene homopolymer having a larger Mn than the propylene homopolymer a-1 but an Rv of 0 when propylene homopolymer was subjected to propylene homopolymerization at 70°C.

[0171] [Table 4]

Claims

1. A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A polypropylene resin (Y) having the following characteristic (Y-1) (excluding the branched polypropylene resin (X)), A polypropylene resin composition comprising 1% by mass to 95% by mass of the resin (X) relative to 100% by mass of the total mass of the resin (X) and the resin (Y). Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.

0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.60 to 0.

75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min.

2. The polypropylene-based resin composition according to claim 1, wherein the polypropylene-based resin (Y) is a homopolymer of propylene.

3. A branched polypropylene resin (X) having the following properties (X-1) to (X-4), A method for producing a polypropylene-based resin composition, comprising: dry-blending a polypropylene-based resin (Y) having the following property (Y-1) (excluding the branched polypropylene-based resin (X)): Property (X-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min to 100 g / 10 min. Property (X-2): The ratio (Mz / Mw) of z-average molecular weight (Mz) to weight-average molecular weight (Mw) obtained by gel permeation chromatography (GPC) is 2.5 to 4.

0. Characteristic (X-3): In the molecular weight distribution curve obtained by 3D-GPC, the absolute molecular weight M abs The branching index g' (million) is 0.60 to 0.

75. Property (X-4): The flow activation energy (Ea) kJ / mol and MFR obtained by measuring dynamic viscoelasticity satisfy the following formula (1). Ea≧−12.5×log(MFR)+66 Formula (1) Property (Y-1): The melt flow rate (MFR) measured at a temperature of 230° C. under a load of 2.16 kg is 0.1 g / 10 min or more and less than 10 g / 10 min.

4. A method for producing a polypropylene resin film, comprising the step of forming a film from the polypropylene resin composition according to claim 1 or 2 by a cast film forming method.

Citation Information

Patent Citations

  • Crystalline synthetic resin composition

    JP1996003364A

  • Crystalline synthetic resin composition

    JP1997118776A

  • Polypropylenic resin composition

    JP2008127487A

  • Polypropylene unstretched film

    JP2011236357A

  • Polypropylene-based resin composition for high rigidity film

    JP2016011380A